Spunbond nonwoven fabric, sanitary material, and method for producing spunbond nonwoven fabric

CN119053738BActive Publication Date: 2026-10-27MITSUI CHEM ASAHI LIFE MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380031357.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-23
Publication Date
2026-10-27
Estimated Expiration
2043-03-23

AI Technical Summary

Benefits of technology

[0047]根据本公开的实施方式,可提供拉伸强度优异且透气度高的纺粘非织造布、卫生材料以及纺粘非织造布的制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005064337490000491
    Figure GDA0005064337490000491
  • Figure GDA0005064337490000501
    Figure GDA0005064337490000501
  • Figure HDA0005064337420000011
    Figure HDA0005064337420000011
Patent Text Reader

Abstract

The spunbond nonwoven fabric of the present disclosure contains fibers formed from a resin composition. The resin composition contains a propylene-based polymer (A), a thermoplastic polyurethane-based elastomer (B), and a polymer (C) modified with at least one polar group selected from the group consisting of an oxygen-containing group, a nitrogen-containing group, a sulfur-containing group, and a phosphorus-containing group. The ratio of the peak intensity of an alpha crystal of the fiber to the crystallinity of the fiber is 10.5 or less. The peak intensity of the alpha crystal represents the peak intensity of the (110) plane of the propylene-based polymer (A) in the vicinity of 2θ = 14° in an X-ray diffraction pattern measured by an X-ray diffractometer using CuKα rays.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to spunbond nonwoven fabrics, sanitary materials, and methods for manufacturing spunbond nonwoven fabrics. Background Technology

[0002] In recent years, nonwoven fabrics made from fibers containing thermoplastic resins have been widely used for various applications due to their excellent breathability, softness, and lightweight properties. Meltblowing and spunbonding are the most widely used manufacturing methods for nonwoven fabrics, as they are suitable for mass production.

[0003] Nonwoven fabrics manufactured by spunbond bonding (hereinafter also referred to as "spunbond nonwoven fabrics") are used in many fields due to their excellent mechanical properties such as tensile strength, stiffness and softness, air permeability, continuous spinning ability, and productivity.

[0004] Thermoplastic resins used in spunbond nonwovens and similar products can be categorized into polyamide resins, polyester resins, and polyolefin resins, based on their melt spinning properties and fiber characteristics. In particular, polyolefin resins, which are inexpensive and have excellent processability, are often used in absorbent materials.

[0005] Patent Document 1 discloses a spunbond nonwoven fabric formed from fibers containing propylene polymers. The spunbond nonwoven fabric disclosed in Patent Document 1 has a melt flow rate (MFR), fineness, mesh weight (weight per unit area), and embossed area ratio within predetermined ranges.

[0006] Patent Document 1: International Publication No. 2007 / 091444 Summary of the Invention

[0007] The problem that the invention aims to solve

[0008] The spunbond nonwoven fabric disclosed in Patent Document 1 still has room for improvement in terms of balancing tensile strength and air permeability.

[0009] The embodiments disclosed herein were made in view of the above circumstances, and the objective is to provide spunbond nonwoven fabrics with excellent tensile strength and high air permeability, sanitary materials, and a method for manufacturing spunbond nonwoven fabrics.

[0010] Methods for solving problems

[0011] The methods for solving the above problems include the following implementation methods.

[0012] <1> A spunbond nonwoven fabric comprising fibers formed from a resin composition,

[0013] The above resin composition comprises a propylene polymer (A), a thermoplastic polyurethane elastomer (B), and a polymer (C).

[0014] The polymer (C) described above is modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups.

[0015] The ratio of the peak intensity of the α crystal of the above-mentioned fiber to the crystallinity of the above-mentioned fiber is 10.5 or less (Intensity [counts] / %).

[0016] The peak intensity of the α crystal described above represents the peak intensity of the (110) plane of the aforementioned propylene polymer (A) near 2θ = 14° in an X-ray diffraction pattern measured by an X-ray diffraction device using CuKα rays.

[0017] <2> A spunbond nonwoven fabric comprising fibers formed from a resin composition,

[0018] The above resin composition comprises a propylene polymer (A), a crystallizing nucleating agent (b), and a polymer (C).

[0019] The polymer (C) described above is modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups.

[0020] The aforementioned fibers have an island-like structure.

[0021] The marine phase contained in the aforementioned island structure includes the aforementioned propylene polymer (A).

[0022] The island phase contained in the aforementioned island structure includes the aforementioned nucleating agent (b).

[0023] The ratio of the peak intensity of the α crystal of the above-mentioned fiber to the crystallinity of the above-mentioned fiber is 10.5 or less [intensity [count] / %].

[0024] The peak intensity of the α crystal described above represents the peak intensity of the (110) plane of the aforementioned propylene polymer (A) near 2θ = 14° in an X-ray diffraction pattern measured by an X-ray diffraction device using CuKα rays.

[0025] <3> In the spunbond nonwoven fabric described in <1> above, the content of the acrylic polymer (A) is 70.0% to 97.0% by mass relative to the total amount of the resin composition.

[0026] The content of the above-mentioned thermoplastic polyurethane elastomer (B) relative to the total amount of the above resin composition is 2.0% to 20.0% by mass.

[0027] The content of the polymer (C) is 1.0% to 10.0% by mass relative to the total amount of the resin composition.

[0028] <4> The spunbond nonwoven fabric described in <1> or <3> above, when viewed under a transmission electron microscope at 25.5 μm... 2 When observing a cross-section orthogonal to the axial direction of the aforementioned fibers using the field of view area,

[0029] The island phase comprising the aforementioned thermoplastic polyurethane elastomer (B) has an average diameter of 0.095 μm or less, and

[0030] The number of island phases comprising the above-mentioned thermoplastic polyurethane elastomer (B) is 200 or more.

[0031] <5> As described in any one of <1> to <4> above, the polar group comprises at least one of an oxygen-containing group and a nitrogen-containing group.

[0032] <6> The spunbond nonwoven fabric as described in any one of <1> to <5> above, wherein the polar group comprises at least one selected from the group consisting of amino, carboxyl, carboxylic anhydride and ester groups.

[0033] <7> As described in <6> above, the spunbond nonwoven fabric contains an amino group as the polar group.

[0034] <8> The spunbond nonwoven fabric as described in any one of <1> to <7> above, wherein the main chain of the polymer (C) comprises a polyolefin or a hydrogenated styrene block copolymer.

[0035] <9> The spunbond nonwoven fabric as described in any one of <1> to <8> above, wherein the propylene polymer (A) comprises a propylene homopolymer with a melting point of 140°C or higher.

[0036] <10> The spunbond nonwoven fabric as described in any one of <1> to <9> above, wherein the resin composition further comprises a density of 0.941 g / cm³. 3 ~0.970g / cm 3 Polyethylene (D).

[0037] <11> As described in <10> above, the content of the polyethylene (D) is 1.0% to 10.0% by mass relative to the total amount of the resin composition in the spunbond nonwoven fabric.

[0038] <12> As described in <10> or <11> above, the spunbond nonwoven fabric, when viewed under a transmission electron microscope at 25.5 μm... 2 When observing a cross-section orthogonal to the axial direction of the aforementioned fibers using the field of view area,

[0039] The island phase containing the aforementioned polyethylene (D) has an average diameter of 0.11 μm or less, and

[0040] The number of island phases containing the aforementioned polyethylene (D) is 150 or more.

[0041] <13> As described in any one of <1> to <12> above, the spunbond nonwoven fabric has a peak intensity of the α crystal of the fiber relative to the crystallinity of the fiber of 8.5 [intensity [count] / %] to 10.5 [intensity [count] / %].

[0042] <14> A sanitary material comprising any one of <1> to <13> above.

[0043] <15> A method for manufacturing a spunbond nonwoven fabric, wherein a resin composition is melt-spun to form a continuous fiber assembly, and the continuous fiber assembly is stretched using cooling air.

[0044] The resin composition described above comprises a propylene polymer (A), a thermoplastic polyurethane elastomer (B), and a polymer (C), wherein the polymer (C) is modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups.

[0045] The air velocity of the aforementioned cooling air is above 3000 m / min.

[0046] Invention Effects

[0047] According to embodiments of this disclosure, spunbond nonwoven fabrics with excellent tensile strength and high air permeability, sanitary materials, and methods for manufacturing spunbond nonwoven fabrics can be provided. Attached Figure Description

[0048] [ Figure 1 ] Figure 1 This is a schematic diagram illustrating an example of a manufacturing apparatus used in a closed-loop spunbond process. Detailed Implementation

[0049] The embodiments of this disclosure will now be described. These descriptions and examples are illustrative of the embodiments and are not intended to limit the scope of the embodiments.

[0050] In this disclosure, a combination of two or more preferred methods is a more preferred method.

[0051] In this disclosure, the numerical range represented by “~” means the range including the values ​​recorded before and after “~” as the lower limit and upper limit.

[0052] In this disclosure, the term "process" includes not only independent processes, but also processes that can be clearly distinguished from other processes, as long as the purpose of the process can be achieved.

[0053] In the numerical ranges described in this disclosure, the upper or lower limit of a numerical range can be replaced by the upper or lower limit of other numerical ranges described in different stages. The upper or lower limit of the numerical ranges described in this disclosure can be replaced by the values ​​shown in the embodiments.

[0054] In this disclosure, each component may comprise multiple corresponding substances. When the amount of each component in the composition is mentioned in this disclosure, in the case where multiple substances equivalent to each component are present in the composition, unless otherwise stated, it means the aggregate amount of the multiple substances present in the composition.

[0055] In this disclosure, "mass%" and "weight%" are synonymous, and "parts by mass" and "parts by weight" are synonymous. In this disclosure, unless otherwise stated, "%" indicating the amount of an ingredient is a mass basis.

[0056] In this disclosure, "Machine Direction (MD)" refers to the direction of travel of the nonwoven web in the nonwoven fabric manufacturing apparatus. "Cross Direction (CD)" refers to the direction that is perpendicular to MD and parallel to the main plane (the plane orthogonal to the thickness direction of the nonwoven fabric).

[0057] In this disclosure, the term "layer" includes not only the case where it is formed in the whole of the region in which the layer exists when observing the region, but also the case where it is formed only in a part of the region.

[0058] In this disclosure, the description of groups (atomic groups) without substitution or non-substitution includes groups without substituents and groups with substituents.

[0059] In this disclosure, "compatibility" refers to the state in which two different substances (especially polymers) are uniformly mixed. Two different substances can be completely compatible or partially compatible.

[0060] (1) First method

[0061] (1.1) Spunbond nonwoven fabric

[0062] The first type of spunbond nonwoven fabric comprises fibers formed from a resin composition. The resin composition comprises: an acrylic polymer (A); a thermoplastic polyurethane elastomer (B); and a polymer (C) modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups (hereinafter also simply referred to as "polymer (C)"). The ratio of the peak intensity of the α-crystal of the fiber to the crystallinity of the fiber (hereinafter also referred to as "ratio (peak intensity / crystallinity)") is 10.5 [(intensity [count]) / %] or less. The peak intensity of the α-crystal represents the peak intensity of the (110) plane of the acrylic polymer (A) near 2θ = 14° in an X-ray diffraction pattern measured by an X-ray diffraction apparatus using CuKα rays.

[0063] In this disclosure, "spunbond nonwoven fabric" refers to a nonwoven fabric made by laminating a continuous fiber assembly spun from a spinneret through the melting or dissolution of a resin composition onto a moving collecting member (e.g., a mesh conveyor) and by one or more bonding methods. Continuous fibers are also called filaments.

[0064] In this disclosure, "polymer modified with polar groups (C)" means a polymer having a main chain containing a hydrocarbon with low polarity and a highly polar group bonded to the main chain.

[0065] In this disclosure, the term "polar group" refers to a group containing one or more heteroatoms. Examples of heteroatoms include oxygen, nitrogen, sulfur, silicon, phosphorus, chlorine, iodine, and bromine atoms.

[0066] In this disclosure, the term "crystallinity of the fiber" is expressed as a percentage (%) of the ratio of the peak area of ​​the crystalline portion to the sum of the peak areas of the crystalline portion and the amorphous portion in the X-ray diffraction pattern of the fiber as measured by an X-ray diffraction apparatus using CuKα rays.

[0067] The spunbond nonwoven fabric of the first embodiment exhibits excellent tensile strength and high air permeability due to its aforementioned structure. In other words, the spunbond nonwoven fabric of the first embodiment has the effect of improving air permeability while maintaining or increasing tensile strength. There is generally an inverse relationship between tensile strength and air permeability.

[0068] This effect is speculated to be based on the following reasons, but is not limited to these.

[0069] Thermoplastic polyurethane elastomers (B) have a higher density than acrylic polymers (A), which can improve the fiber strength of spunbond nonwovens. Therefore, in spunbond nonwovens, the strength can be maintained even with a reduction in the amount of fiber per unit volume.

[0070] However, in incompatible resin compositions formed by adding only thermoplastic polyurethane elastomer (B) to propylene polymer (A), the two may be incompatible. This is presumably because propylene polymer (A) is a low-polarity resin, while thermoplastic polyurethane elastomer (B) is a high-polarity resin, resulting in poor compatibility. Consequently, in the crystal structure of fibers formed from incompatible resin compositions, the island phases of thermoplastic polyurethane elastomer (B) are larger. Therefore, if the manufacturing apparatus used in spunbonding (hereinafter also referred to as "the apparatus") is used to fiberize the incompatible resin composition, it is possible that the fibers will experience localized loads, preventing the fiberization of the incompatible resin composition.

[0071] Therefore, in the first embodiment, the resin composition contains polymer (C) in addition to the acrylic polymer (A) and the thermoplastic polyurethane elastomer (B). This improves the compatibility between the acrylic polymer (A) and the thermoplastic polyurethane elastomer (B). It is presumed that this is because the main chain of polymer (C) has a high affinity for the acrylic polymer (A), while the polar groups of polymer (C) have a high affinity for the thermoplastic polyurethane elastomer (B), thus polymer (C) functions as a compatibilizer. Consequently, in the crystal structure of the fiber formed from the resin composition of the first embodiment, the island phases of the thermoplastic polyurethane elastomer (B) become micro-dispersed (i.e., the average diameter of the island phases becomes smaller, and the number of island phases increases). In other words, fibers with a more uniform crystal structure (i.e., fibers with a more uniform structure) can be obtained. Therefore, the fibers are more uniformly dispersed and accumulated on the moving collecting surface of the device. It is presumed that this results in high air permeability of the spunbond nonwoven fabric.

[0072] Furthermore, in the first embodiment, the ratio (peak intensity / crystallinity) is 10.5 or less [strength [count] / %]. A ratio (peak intensity / crystallinity) of 10.5 or less [strength [count] / %] not only indicates that the amount of α-crystals in the acrylic polymer (A) is relatively less compared to fibers composed of incompatible resin compositions, but also that there is less clear boundary between the hard crystalline phase and the soft amorphous phase, the ordered structural change of the acrylic polymer (A) and the thermoplastic polyurethane elastomer (B) is continuous, and the crystal structure of the fiber itself is relatively uniform. Therefore, the fiber has higher strength. It is speculated that as a result, the spunbond nonwoven fabric exhibits excellent tensile strength.

[0073] Based on the above inferences, the spunbond nonwoven fabric of the first method has excellent tensile strength and high air permeability.

[0074] (1.1.1) Fiber

[0075] The first type of spunbond nonwoven fabric contains fibers.

[0076] (1.1.1.1) Ratio (peak intensity / crystallinity)

[0077] The ratio (peak intensity / crystallinity) is 10.5 or less [intensity [count] / %]. The peak intensity of α crystals represents the peak intensity of the (110) plane of the aforementioned propylene polymer (A) near 2θ = 14° in an X-ray diffraction pattern measured by an X-ray diffraction apparatus using CuKα rays.

[0078] The methods for determining the crystallinity of the fiber and the peak intensity of the α crystal of the fiber are the same as those described in the examples.

[0079] The peak intensity / crystallinity ratio represents the amount of α-crystal per unit crystal. A smaller peak intensity / crystallinity ratio means a smaller amount of complete α-crystal per unit crystal. That is, it is considered that the boundary between the crystalline phase (and amorphous phase) of the propylene polymer (A) and the crystalline phase (and amorphous phase) of the thermoplastic polyurethane elastomer (B) is small, and they form a homogeneous crystalline system.

[0080] The ratio (peak intensity / crystallinity) is below 10.5 [strength [count] / %]. As a result, the spunbond nonwoven fabric exhibits superior tensile strength and higher air permeability.

[0081] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the ratio (peak strength / crystallinity) is preferably 8.5 [strength [count] / %] to 10.5 [strength [count] / %].

[0082] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the ratio (peak strength / crystallinity) is more preferably 10.3 [strength [count] / %] or less, more preferably 10.0 [strength [count] / %] or less, and particularly preferably 9.7 [strength [count] / %] or less.

[0083] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the ratio (peak strength / crystallinity) is more preferably 8.8 [strength [count] / %] or higher, more preferably 9.0 [strength [count] / %] or higher, and particularly preferably 9.2 [strength [count] / %] or higher.

[0084] As a method to adjust the ratio (peak intensity / crystallinity) to below 10.5 [intensity [count] / %], the manufacturing method of spunbond nonwoven fabric described later can be cited as an example.

[0085] The peak intensity of the α crystal of the fiber is not particularly limited, but from the viewpoint of improving the tensile strength of spunbond nonwoven fabric, it is preferably 500 [strength count] to 570 [strength count], more preferably 510 [strength count] to 560 [strength count], and even more preferably 520 [strength count] to 550 [strength count].

[0086] As a method for adjusting the peak intensity of the α crystal of the fiber to the above-mentioned range, for example, the manufacturing method of spunbond nonwoven fabric described later can be cited.

[0087] The crystallinity of the fiber is not particularly limited, but from the viewpoint of improving the tensile strength of spunbond nonwoven fabric, it is preferably 50% to 60%, more preferably 51% to 58%, and even more preferably 52% to 56%.

[0088] As a method for adjusting the crystallinity of fibers to the above-mentioned range, for example, the manufacturing method of spunbond nonwoven fabric described later can be cited.

[0089] (1.1.1.2) Island structure

[0090] In the first approach, the fibers can have an island structure.

[0091] In this disclosure, the term "fiber having an island structure" means that the cross-section of a fiber cut in a direction orthogonal to the fiber's axial direction has an island structure.

[0092] In this disclosure, the term "island structure" refers to a phase-separated structure in which a phase containing at least two components (i.e., an island phase) exists (e.g., dispersed) in a continuous phase (i.e., a marine phase) composed of another component.

[0093] Hereinafter, "fibers with island-island structures" will also be referred to as "island-island fibers".

[0094] In the first embodiment, the island-island fiber is formed from a resin composition. The resin composition comprises a propylene-based polymer (A), a thermoplastic polyurethane-based elastomer (B), and a polymer (C), and may further comprise polyethylene (D) if desired. Details regarding the resin composition will be described later.

[0095] Island structures have marine facies and multiple island facies. Multiple island facies exist (e.g., dispersed) within the marine facies.

[0096] Preferably, the marine phase comprises a propylene polymer (A), and each of the plurality of island phases comprises a thermoplastic polyurethane elastomer (B). When the resin composition further comprises polyethylene (D), the marine phase preferably comprises a propylene polymer (A), and each of the plurality of island phases comprises an island phase of thermoplastic polyurethane elastomer (B) and an island phase of polyethylene (D).

[0097] The fiber diameter of the island-island fiber is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 28 μm or less. The smaller the fiber diameter, the better the softness of the nonwoven fabric. From an operational point of view, the fiber diameter of the island-island fiber is preferably 10 μm or more. The island-island fiber can be a long fiber (short fiber) or a single fiber (filament). Furthermore, there are no particular limitations on the cross-sectional shape of the island-island fiber; for example, circular, elliptical, and irregular cross-sections are possible.

[0098] (1.1.1.2.1) Island phase of thermoplastic polyurethane elastomer (B)

[0099] Using a transmission electron microscope at 25.5 μm 2 When observing a cross-section orthogonal to the fiber axis in the field of view, it is preferable that the average diameter of the island phase containing the thermoplastic polyurethane elastomer (B) is 0.095 μm or less, and the number of island phases containing the thermoplastic polyurethane elastomer (B) is 200 or more. This improves spinnability.

[0100] There is no particular limitation on the magnification of a transmission electron microscope (TEM), which can be appropriately adjusted to the extent that the size and number of island phases in the fiber cross-section can be determined. For example, the magnification of a TEM can be 40,000x.

[0101] The methods for determining the average diameter of the island phase containing the thermoplastic polyurethane elastomer (B) and the number of island phases containing the thermoplastic polyurethane elastomer (B) are the same as those described in the examples.

[0102] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the average diameter of the island phase containing thermoplastic polyurethane elastomer (B) is more preferably 0.070 μm to 0.093 μm, further preferably 0.075 μm to 0.090 μm, and particularly preferably 0.078 μm to 0.087 μm.

[0103] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the number of island phases containing thermoplastic polyurethane elastomer (B) is more preferably 210 to 800, further preferably 215 to 700, and particularly preferably 220 to 650.

[0104] The ratio of the island phase area to the total cross-sectional area of ​​the island-island fibers (hereinafter referred to as the "island phase area ratio") is preferably 1.0% to 20%. By setting it within the above range, the orientation crystallization of the propylene polymer (A) within the island-island fibers is easily hindered. As a result, the elongation and spinnability of the spunbond nonwoven fabric are more excellent.

[0105] (1.1.1.2.2) Island phase of polyethylene (D)

[0106] When the resin composition further comprises polyethylene (D), the sample was analyzed using a transmission electron microscope at 25.5 μm. 2 When observing a cross-section orthogonal to the fiber axis in the field of view, it is preferable that the average diameter of the island phase containing polyethylene (D) is 0.11 μm or less, and the number of island phases containing polyethylene (D) is 150 or more. This improves spinnability and increases maximum elongation.

[0107] There is no particular limitation on the magnification of a transmission electron microscope (TEM), which can be appropriately adjusted to the extent that the size and number of island phases in the fiber cross-section can be determined. For example, the magnification of a TEM can be 40,000x.

[0108] The methods for determining the average diameter of the island phase containing polyethylene (D) and the number of island phases containing polyethylene (D) are the same as those described in the examples.

[0109] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics and improving the maximum elongation, the average diameter of the island phase containing polyethylene (D) is more preferably 0.06 μm to 0.11 μm, further preferably 0.07 μm to 0.105 μm, and particularly preferably 0.08 μm to 0.105 μm.

[0110] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics and improving the maximum elongation, the number of island phases containing polyethylene (D) is more preferably 150 to 400, further preferably 160 to 350, and particularly preferably 165 to 300.

[0111] (1.1.1.3) Morphology, etc.

[0112] The fibers contained in spunbond nonwoven fabrics can be either solid fibers or hollow fibers. From the viewpoint of maintaining the strength of spunbond nonwoven fabrics while reducing fineness, the fibers contained in spunbond nonwoven fabrics are preferably solid fibers. As for the manufacturing method of hollow fibers, methods described in known literature can be appropriately referred to.

[0113] The form of fibers contained in spunbond nonwoven fabrics is not particularly limited; they can be composite fibers or single-component fibers. Composite fibers preferably contain two or more thermoplastic resins as constituent components.

[0114] Examples of composite fibers include core-sheath type, parallel type, and island type composite fibers. Core-sheath type composite fibers only need to have a core and a sheath, and can be either concentric core-sheath type or eccentric core-sheath type. In eccentric core-sheath type composite fibers, the core may be exposed on the surface or may not be exposed on the surface.

[0115] The fibers contained in spunbond nonwoven fabrics can be crimped or non-crimped fibers. Non-crimped fibers can be, for example, eccentric core-sheath crimped composite fibers.

[0116] (1.1.2) Resin Composition

[0117] The fibers are formed from a resin composition.

[0118] The resin composition comprises an acrylic polymer (A), a thermoplastic polyurethane elastomer (B), and a polymer (C). Details of each of the acrylic polymer (A), thermoplastic polyurethane elastomer (B), and polymer (C) will be described later.

[0119] The content of the propylene polymer (A) relative to the total amount of the resin composition is preferably 70.0% to 97.0% by mass, the content of the thermoplastic polyurethane elastomer (B) relative to the total amount of the resin composition is preferably 2.0% to 20.0% by mass, and the content of the polymer (C) relative to the total amount of the resin composition is preferably 1.0% to 10.0% by mass. This improves spinnability while maintaining the tensile strength and air permeability of the spunbond nonwoven fabric.

[0120] (1.1.2.1) Propylene polymers (A)

[0121] The resin composition comprises an propylene polymer (A).

[0122] The propylene polymer (A) comprises building blocks derived from propylene. Specifically, the propylene polymer (A) comprises propylene homopolymers and copolymers of propylene with α-olefins other than propylene (hereinafter also referred to as "propylene-α-olefin copolymers"). The propylene polymer (A) may be, for example, a propylene homopolymer, a propylene-α-olefin copolymer, or both.

[0123] The propylene polymer (A) can be used in the resin composition either as a single component or in combination of two or more components.

[0124] The propylene-α-olefin copolymer is preferably a copolymer of propylene and one or more α-olefins other than propylene that have 2 to 10 carbon atoms, and more preferably a copolymer of propylene and one or more α-olefins other than propylene that have 2 to 8 carbon atoms.

[0125] From the viewpoint of excellent flexibility, specific examples of preferred α-olefins for copolymerization with propylene include ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, and 4-methyl-1-hexene.

[0126] Examples of propylene-α-olefin copolymers include propylene-ethylene copolymers and propylene-ethylene-1-butene copolymers. The content of α-olefin-derived constituent units in the propylene-α-olefin copolymer is not particularly limited, but is preferably 1 mol% to 10 mol%, more preferably 1 mol% to 5 mol%. The propylene polymer (A) may be used alone in the resin composition, or two or more may be used in combination.

[0127] The melting point (Tm) of the propylene polymer (A) is not particularly limited, but is preferably 120°C to 165°C, more preferably 130°C to 165°C, and even more preferably 150°C to 165°C.

[0128] When the propylene polymer (A) is a propylene homopolymer, the melting point (Tm) of the propylene polymer (A) is preferably 140°C or higher, more preferably 155°C or higher, and even more preferably 157°C to 165°C.

[0129] When the propylene polymer (A) is a propylene-α-olefin copolymer, the melting point (Tm) of the propylene polymer (A) is preferably below 153°C, and more preferably 125°C to 150°C.

[0130] In this disclosure, the melting point (Tm) can be determined using differential scanning calorimetry (DSC) as follows: Using a Perkin Elmer DSC Pyris1 or a SII Nanotechnology DSC7020 as a differential scanning calorimeter (DSC), under a nitrogen atmosphere (20 ml / min), the sample (approximately 5 mg) is heated from room temperature to 200 °C at 10 °C / min, held at that temperature for 5 minutes, cooled to -50 °C at 10 °C / min and held at -50 °C for 5 minutes, and then heated a second time at 10 °C / min to 200 °C. The melting point (Tm) is calculated from the peak of the crystal melting peak observed during this second heating process. It should be noted that if multiple crystal melting peaks are observed, the high-temperature side peak is taken as the melting point (Tm).

[0131] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the propylene polymer (A) preferably includes a propylene homopolymer with a melting point (Tm) of 140°C or higher, and more preferably a propylene homopolymer with a melting point (Tm) of 140°C or higher.

[0132] Regarding the melt flow rate (MFR) of the propylene polymer (A), there is no particular limitation as long as it can be used to manufacture spunbond nonwoven fabrics. However, from the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, it is preferred to be 10 g / 10 min to 100 g / 10 min, more preferably 15 g / 10 min to 90 g / 10 min, and even more preferably 20 g / 10 min to 80 g / 10 min.

[0133] The melt flow rate of the propylene polymer (A) was determined according to ASTM standard D-1238. The melt flow rate of the propylene polymer (A) was determined under the following conditions: 230°C and a load of 2.16 kg.

[0134] Regarding the density of the propylene polymer (A), there are no particular limitations as long as melt spinning is possible, but 0.900 g / cm³ is preferred. 3 ~0.945g / cm 3 More preferably, it is 0.905 g / cm³. 3 ~0.940g / cm 3 .

[0135] The density of propylene polymer (A) can be determined according to JIS K7112 (density gradient tube method).

[0136] Propylene polymers (A) can be obtained by polymerizing propylene as a raw material using known catalysts such as Ziegler-Natta catalysts and metallocene catalysts. Among these, Ziegler-Natta catalysts are preferred to eliminate heterogeneous bonding. This allows for polymerization with high stereoregularity.

[0137] As for the polymerization method of propylene, any well-known method can be used. For example, methods that polymerize in inactive solvents such as hexane, heptane, toluene, and xylene can be used; methods that polymerize in liquid monomers can be used; methods that polymerize in gaseous monomers with the addition of a catalyst and in the gas phase can be used; or methods that combine these methods to polymerize.

[0138] Acrylic polymers (A) can be commercially available products.

[0139] From the viewpoint of balancing the strength and air permeability of spunbond nonwoven fabrics, the content of propylene polymer (A) relative to the total amount of resin composition is preferably 70.0% to 97.0% by mass, more preferably 72.0% to 94.0% by mass, and even more preferably 75.0% to 90.0% by mass.

[0140] (1.1.2.1.1) Polymers derived from biomass

[0141] As the thermoplastic polyurethane elastomer disclosed herein, a thermoplastic polyurethane elastomer comprising biomass-derived raw materials can also be used (biomass-derived thermoplastic polyurethane elastomer). The biomass-derived thermoplastic polyurethane elastomer can also be obtained by polymerizing isopropanol obtained from biomass raw materials, primarily non-edible plants such as sorrel, through fermentation, followed by dehydration of the isopropanol to obtain propylene.

[0142] In this disclosure, "biomass content" refers to the percentage of carbon derived from biomass, calculated by measuring radioactive carbon (C14). It is known that atmospheric carbon dioxide contains C14 in a certain proportion (approximately 105.5 pMC), therefore, plants that absorb atmospheric carbon dioxide (such as corn) also contain approximately 105.5 pMC of C14. Furthermore, it is known that fossil fuels contain almost no C14. Therefore, by measuring the proportion of C14 contained in all carbon atoms in the feedstock, the percentage of carbon derived from biomass in the feedstock can be calculated.

[0143] For example, if the C14 content in the raw material is set as PC14, the carbon content Pbio (%) of the raw material derived from biomass can be calculated using the following formula (1).

[0144] Pbio(%) = PC14 / 105.5 × 100 ··· Equation (1)

[0145] That is, if all the raw materials for polyurethane are derived from biomass, then theoretically the carbon content derived from biomass is 100%, and therefore the biomass degree of bioplastic polyurethane elastomers derived from biomass is 100%. Furthermore, since raw materials derived from fossil fuels contain almost no C14, the carbon content derived from biomass in polyurethane made solely from fossil fuel raw materials is 0%, and the biomass degree of polyurethane derived from fossil fuels is 0.

[0146] The biomass content of the polyurethane-based thermoplastic elastomer derived from biomass used as the raw material for the spunbond nonwoven fabric disclosed herein is preferably 1% or more.

[0147] Generally, thermoplastic polyurethane elastomers include: polymer diols such as polyether polyols, polyester polyols, and polycarbonate polyols; short-chain diols (chain extenders) such as aliphatic diols, aromatic diols, and alicyclic diols; and isocyanate compounds such as aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates as raw materials. In this disclosure, preferred isocyanates include aliphatic isocyanates and aromatic isocyanates such as 1,5-pentamethylene diisocyanate-based polyisocyanate (trade name: Stabio (registered trademark)) manufactured by Mitsui Chemicals Co., Ltd.

[0148] In cases where the raw materials of the spunbond nonwoven fabric disclosed herein include recycled polymers, the thermoplastic polyurethane elastomer used as the raw material of the spunbond nonwoven fabric disclosed herein may contain so-called recycled polymers obtained through recycling.

[0149] "Recycled polymer" means a substance comprising a polymer obtained through the recycling of waste polymer articles, for example, which may be manufactured by the method described in DE102019127827(A1). Recycled polymer may contain a mark that identifies it as having been obtained through recycling.

[0150] (1.1.2.2) Thermoplastic polyurethane elastomers (B)

[0151] The resin composition contains a thermoplastic polyurethane elastomer (B).

[0152] Thermoplastic polyurethane elastomers (B) can, for example, have hard segments and amorphous soft segments with low glass transition temperatures. In the hard segments, at least the polyurethane forms pseudo-crosslinks through physical aggregation. The soft segments are formed from polymers such as block copolymers. Block copolymers are composed of polycarbonate-based polyols, ether-based polyols, caprolactone-based polyesters, and adipate-based polyesters, etc.

[0153] As a thermoplastic polyurethane elastomer (B), specifically, urethane-based thermoplastic elastomers (TPU) as specified in JIS K 6418:2007 can be cited.

[0154] Thermoplastic polyurethane elastomers (B) have a higher density than polyolefins, which can improve the fiber strength of spunbond nonwovens. Therefore, even if the amount of fibers per unit volume of spunbond nonwovens is reduced (a factor that improves air permeability), the strength of the spunbond nonwovens can be maintained. If the content of thermoplastic polyurethane elastomers (B) is high, the strength of the spunbond nonwovens is further improved.

[0155] The melting point (Tm) of the thermoplastic polyurethane elastomer (B) was determined using a differential scanning calorimeter (DSC). Specifically, using a differential scanning calorimeter (Perkin Elmer, DSC-7), a 5 mg sample was held at -100°C for 5 minutes under a nitrogen atmosphere, and then heated at 10°C / min. The temperature of the peak observed on the highest temperature side of the resulting melting endothermic curve was taken as the melting point (Tm) of the thermoplastic polyurethane elastomer (B).

[0156] The melting point (Tm) of the thermoplastic polyurethane elastomer (B) is not particularly limited, but is preferably below 165°C, and more preferably below 163°C.

[0157] The heat of fusion of the thermoplastic polyurethane elastomer (B) is a value determined using a differential scanning calorimeter (DSC). Specifically, the heat of fusion is determined by using a differential scanning calorimeter (Perkin Elmer, DSC-7), holding a 5 mg sample at -100°C for 5 minutes under a nitrogen atmosphere, and then heating it at 10°C / min. The heat of fusion obtained from the resulting melting endothermic curve is the heat of fusion determined from the maximum endothermic peak.

[0158] There is no particular limitation on the heat of fusion of the thermoplastic polyurethane elastomer (B), but it is preferably 14.0 mJ / mg or less, and more preferably 12.0 mJ / mg or less.

[0159] The solidification initiation temperature of the thermoplastic polyurethane elastomer (B) is preferably 65°C to 195°C, more preferably 75°C to 195°C, and even more preferably 85°C to 195°C.

[0160] If the solidification initiation temperature is above 65°C, poor molding conditions such as fiber fusion, filament breakage, and resin blockage can be suppressed when obtaining spunbond nonwoven fabric. Furthermore, during hot embossing, the molded spunbond nonwoven fabric can be prevented from wrapping around the embossing roller. The resulting spunbond nonwoven fabric has low viscosity, making it suitable for use as clothing, hygiene products, sports materials, and other materials that come into contact with the skin. On the other hand, by setting the solidification initiation temperature below 195°C, molding processability can be improved. It should be noted that the solidification initiation temperature of the molded fibers tends to be higher than that of the thermoplastic polyurethane elastomer (B) used as the fiber raw material.

[0161] The solidification onset temperature of the thermoplastic polyurethane elastomer (B) was determined using a differential scanning calorimeter (DSC). Specifically, the thermoplastic polyurethane elastomer (B) was heated to 230°C at a rate of 10°C / min, held at 230°C for 5 minutes, and then cooled at a rate of 10°C / min. The onset temperature of the exothermic peak originating from the solidification of the thermoplastic polyurethane elastomer (B) at this point is defined as the solidification onset temperature of the thermoplastic polyurethane elastomer (B).

[0162] To adjust the solidification initiation temperature of the thermoplastic polyurethane elastomer (B) to 65°C or higher, the polyol, isocyanate compound, and chain extender used as raw materials for the thermoplastic polyurethane elastomer (B) must each be selected as having an optimal chemical structure, and the amount of hard segments must be adjusted. "Hard segment amount" refers to the mass percentage (mass%) obtained by dividing the total mass of the isocyanate compound and chain extender used in the manufacture of the thermoplastic polyurethane elastomer (B) by the total mass of the polyol, isocyanate compound, and chain extender, and then multiplying by 100. The hard segment amount is preferably 20% to 60% by mass, more preferably 22% to 50% by mass, and even more preferably 25% to 48% by mass.

[0163] The number of particles of the polar solvent-insoluble component in the thermoplastic polyurethane elastomer (B) is preferably 3 million or less (3 million particles / g) relative to 1g of thermoplastic polyurethane elastomer (B), more preferably 2.5 million or less / g, and even more preferably 2 million or less / g.

[0164] The term "polar solvent-insoluble components in thermoplastic polyurethane elastomers (B)" mainly refers to lumps (e.g., fish eyes, gels, etc.) generated during the manufacturing of thermoplastic polyurethane elastomers (B).

[0165] By reducing the number of particles of the polar solvent-insoluble component to below 3 million / g, it is possible to further suppress the increase in fiber diameter distribution and the occurrence of problems such as fiber breakage during spinning within the solidification initiation temperature range of thermoplastic polyurethane elastomer (B).

[0166] Examples of components that are insoluble in polar solvents include: components derived from hard segment aggregates of thermoplastic polyurethane elastomer (B); components formed by cross-linking of hard and / or soft segments through urethane bonds, biuret bonds, etc.; and components generated from the raw materials constituting thermoplastic polyurethane elastomer (B) and chemical reactions between the raw materials.

[0167] The number of particles insoluble in polar solvents is obtained by measuring the insoluble components when thermoplastic polyurethane elastomer (B) is dissolved in dimethylacetamide solvent using a particle size distribution measuring device with a 100 μm sieve. If a 100 μm sieve is installed, the number of particles from 2 μm to 60 μm in size, converted to uncrosslinked polystyrene, can be measured.

[0168] Thermoplastic polyurethane elastomers (B) with low polar solvent insoluble components can be obtained by filtration after polymerization of polyols, isocyanate compounds and chain extenders.

[0169] From the viewpoint of suppressing the introduction of air bubbles into the strands and the occurrence of filament breakage when forming spunbond nonwoven fabrics using large spunbond molding equipment, the moisture content of the thermoplastic polyurethane elastomer (B) is preferably 350 ppm or less, more preferably 300 ppm or less, and even more preferably 150 ppm or less.

[0170] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, in thermoplastic polyurethane elastomers (B), it is preferable that the sum of the heats of fusion (a) and the sum of the heats of fusion (b) satisfy the relationship of the following equation (B1), more preferably the relationship of the following equation (B2), and even more preferably the relationship of the following equation (B3). The sum of the heats of fusion (a) and the sum of the heats of fusion (b) are measured using a differential scanning calorimeter (DSC). The sum of the heats of fusion (a) is obtained from the endothermic peak with a peak temperature in the range of 90°C to 140°C. The sum of the heats of fusion (b) is obtained from the endothermic peak with a peak temperature in the range of more than 140°C and less than 220°C.

[0171] Equation (B1): a / (a+b)≤0.8

[0172] Equation (B2): a / (a+b)≤0.7

[0173] Equation (B3): a / (a+b)≤0.6

[0174] "a / (a+b)" means the ratio of the heat of fusion of the hard domain of the thermoplastic polyurethane elastomer (B).

[0175] If the heat of fusion ratio (a / (a+b)) of the hard region of the thermoplastic polyurethane elastomer (B) is 0.8 or less, the tensile strength and air permeability of the spunbond nonwoven fabric can be balanced. In this disclosure, the lower limit value of the heat of fusion ratio (a / (a+b)) of the hard region of the thermoplastic polyurethane elastomer (B) is preferably about 0.1.

[0176] The melt viscosity of the thermoplastic polyurethane elastomer (B) is preferably 100 Pa·s to 3000 Pa·s, more preferably 200 Pa·s to 2000 Pa·s, and even more preferably 900 Pa·s to 1600 Pa·s.

[0177] Melt viscosity was measured using a Capilograph (manufactured by Toyo Seiki Co., Ltd.), employing an instrument with a nozzle length of 30 mm and a diameter of 1 mm. The measurement conditions were a temperature of 200°C and a shear rate of 100 sec. -1 .

[0178] Thermoplastic polyurethane elastomers (B) with such properties can be obtained, for example, by the manufacturing method described in Japanese Patent Application Publication No. 2004-244791.

[0179] Spunbond nonwoven fabrics molded using thermoplastic polyurethane elastomers (B) have an excellent tactile feel, making them suitable for applications involving skin contact, such as hygiene products. The filter installed inside the extruder to remove impurities is less prone to clogging, reducing the frequency of equipment adjustments and maintenance, making it a preferred choice for industrial applications.

[0180] Thermoplastic polyurethane elastomer (B) can be used in the resin composition as a single type or in combination of two or more types.

[0181] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the content of thermoplastic polyurethane elastomer (B) relative to the total amount of the resin composition is preferably 2.0% to 20.0% by mass, more preferably 2.5% to 19.0% by mass, and even more preferably 3.0% to 18.0% by mass.

[0182] (1.1.2.3) Polymer (C)

[0183] The resin composition contains a polymer (C).

[0184] Polymer (C) functions as a compatibilizer to make acrylic polymer (A) and thermoplastic polyurethane elastomer (B) compatible. Because the resin composition contains polymer (C), it is possible to prepare a resin composition containing acrylic polymer (A) and thermoplastic polyurethane elastomer (B) with the compounding components fully dissolved.

[0185] Polymer (C) has been modified with polar groups. In other words, polymer (C) has a main chain and polar groups bonded to the main chain. Polymer (C) can be used alone in the resin composition, or two or more can be used in combination.

[0186] (1.1.2.3.1) Polar groups

[0187] The polar group is selected from at least one of the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups.

[0188] Examples of oxygen-containing groups include, for example: alkoxy, aryloxy, ester, ether, acyl, carboxyl, carbonate, hydroxyl, peroxy, and carboxylic anhydride (-CO-O-CO-); substituted carboxyl groups, etc.

[0189] Examples of nitrogen-containing groups include: amino, alkylamino, arylamino, alkylarylamino, imino, alkylimino, arylimino, imide, substituted imide, amide, substituted amide, hydrazine, hydrazine, nitro, nitroso, cyano, isocyano, cyanate, amidine, diazo, and amino, alkylamino, arylamino; as well as alkylarylamino groups that have become ammonium salts.

[0190] As an alkylamino group, dimethylamino or methylethylamino is preferred. As an arylamino group, diphenylamino is preferred. As an alkylimino group, methylimino, ethylimino, propylimino, or butylimino is preferred. As an arylimino group, phenylimino is preferred. As a substituted imide group, acetylimino or benzoimino is preferred. As a substituted amide group, acetamido, N-methylacetamido, or N-methylbenzoamide is preferred.

[0191] Examples of sulfur-containing groups include mercapto, thioester, dithioester, alkylthio, arylthio, thioacyl, thioether, thiocyanate, isothiocyanate, sulfonyl, sulfonamide, thiocarboxyl, dithiocarboxyl, sulfonyl, sulfonyl, sulfinyl group, and sulfenyl group.

[0192] As an alkylthio group, methylthio or ethylthio is preferred. As an arylthio group, phenylthio, methylphenylthio, or naphthio is preferred. As a thioester group, acetylthio, benzoylthio, methylthiocarbonyl, or phenylthiocarbonyl is preferred. As a sulfonyl ester group, methyl sulfonate, ethyl sulfonate, or phenyl sulfonate is preferred. As a sulfonamide group, phenylsulfonamide, N-methylsulfonamide, or N-methyl-p-toluenesulfonamide is preferred.

[0193] Examples of phosphorus-containing groups include, for example, phosphide groups, phosphoryl groups, thiophosphoryl groups, and phosphate ester groups.

[0194] The polar group preferably includes at least one of an oxygen-containing group and a nitrogen-containing group. This improves spinnability while maintaining the tensile strength and air permeability of the spunbond nonwoven fabric.

[0195] The polar group preferably includes at least one selected from the group consisting of amino, carboxyl, carboxylic anhydride, and ester groups. This improves spinnability while maintaining the tensile strength and air permeability of the spunbond nonwoven fabric.

[0196] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the polar group is further preferably composed of at least one selected from the group consisting of amino and carboxylic anhydride groups, and particularly preferably contains an amino group.

[0197] (1.1.2.3.2) Main chain

[0198] Examples of polymers with a main chain (C) include polyolefins and polystyrene. Polystyrene includes hydrogenated styrene-based block copolymers.

[0199] Polyolefins include: α-olefins with 2 to 20 carbon atoms, preferably 2 to 6, such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, and 4-methyl-1-pentene; and homopolymers or copolymers of chain or cyclic polyenes such as cyclopentene, cyclohexene, 1,4-hexadiene, 1,5-hexadiene, divinylbenzene, 1,3-cyclopentadiene, 1,3-cyclohexadiene, and 5-vinyl-2-norbornene.

[0200] The main chain of polymer (C) preferably contains polyolefin or hydrogenated styrene-based block copolymer. This improves spinnability while maintaining the tensile strength and air permeability of spunbond nonwoven fabrics.

[0201] Polymer (C) can be a commercially available product.

[0202] Commercially available products that are hydrogenated styrene block copolymers with carboxylic anhydride or amino groups as polar groups include the Tuftec M series (manufactured by Asahi Kasei Corporation).

[0203] Commercially available polyolefins with carboxylic anhydride groups as polar groups include UMEX (manufactured by Sanyo Chemical Co., Ltd.) and ADMER (manufactured by Mitsui Chemicals Co., Ltd.).

[0204] Commercially available polyolefins with carboxyl groups as polar groups include NUCREL (manufactured by Mitsui DuPont Chemicals Co., Ltd.).

[0205] Commercially available polyolefins with ester groups as polar groups include ACRYFT (manufactured by Sumitomo Chemical Co., Ltd.).

[0206] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the content of polymer (C) relative to the total amount of resin composition is preferably 1.0% to 10.0% by mass, more preferably 1.5% to 9.0% by mass, and even more preferably 2.0% to 7.0% by mass.

[0207] (1.1.2.4) Polyethylene (D)

[0208] The resin composition may contain polyethylene (D). This improves the elongation of spunbond nonwoven fabrics.

[0209] Polyethylene (D) comprises constituent units derived from ethylene. Examples of polyethylene (D) include, for instance, high-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE), all homopolymers of ethylene. Polyethylene (D) can be used alone or in combination in a resin composition.

[0210] The resin composition preferably further comprises a density of 0.941 g / cm³. 3 ~0.970g / cm 3 Polyethylene (D). This allows for a balance between the tensile strength and air permeability of spunbond nonwovens, while also increasing the maximum elongation.

[0211] From the viewpoint of further improving the elongation of spunbond nonwoven fabrics, the density of polyethylene (D) is preferably 0.941 g / cm³. 3 ~0.970g / cm 3 More preferably, it is 0.945 g / cm³. 3 ~0.960g / cm 3 .

[0212] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics and improving the maximum elongation, the content of polyethylene (D) relative to the total amount of the resin composition is preferably 1.0% to 10.0% by mass, more preferably 3.0% to 9.0% by mass.

[0213] (1.1.2.5) Low molecular weight olefin polymers (E)

[0214] The resin composition may contain low molecular weight olefin polymers (E).

[0215] Low molecular weight olefin polymers (E) are olefin polymers with a weight average molecular weight of 500 to 30,000, and are polymers that do not belong to any of the following: propylene polymers (A), thermoplastic polyurethane elastomers (B), polymers (C), and polyethylene (D).

[0216] Low molecular weight olefin polymers (E) can be used in resin compositions in one or in combination of two or more.

[0217] When the resin composition contains polyethylene (D) and a low molecular weight olefin polymer (E), the dispersibility of the propylene polymer (A) and polyethylene (D) is improved. As a result, there is a tendency for improved elongation and spinnability of spunbond nonwoven fabrics.

[0218] The following description of the low molecular weight olefin polymer (E) will explain the case where the resin composition further contains polyethylene (D).

[0219] Low molecular weight olefin polymers (E) may contain building blocks derived from one olefin or from two or more olefins.

[0220] The low molecular weight olefin polymer (E) is a waxy polymer. The weight-average molecular weight (Mw) of the low molecular weight olefin polymer (E) is preferably lower than that of the propylene polymer (A) and polyethylene (D).

[0221] The weight-average molecular weight (Mw) of low molecular weight olefin polymers (E) is 500–30,000.

[0222] If the weight-average molecular weight (Mw) of the low molecular weight olefin polymer (E) is within the above range, the dispersibility of the propylene polymer (A) and polyethylene (D) is further improved. As a result, the spunbond nonwoven fabric exhibits superior elongation and spinnability.

[0223] The weight-average molecular weight (Mw) of the low molecular weight olefin polymer (E) is 30,000 or less, preferably less than 15,000, more preferably less than 10,000, even more preferably less than 6,000, particularly preferably less than 6,000, even more preferably less than 5,000, even more preferably less than 3,000, even more preferably less than 2,000, and even more preferably less than 1,500.

[0224] The weight-average molecular weight (Mw) of the low molecular weight olefin polymer (E) is 500 or more, preferably 700 or more, and more preferably 1000 or more.

[0225] In the determination of the weight-average molecular weight (Mw) of low molecular weight olefin polymers (E), gel permeation chromatography (GPC) is used. The preferred GPC conditions are those shown below. The weight-average molecular weight (Mw) of the low molecular weight olefin polymers (E) is determined, for example, by preparing a standard curve using commercially available monodisperse standard polystyrene and based on the conversion method described below.

[0226] [Measurement Conditions]

[0227] Chromatographic columns: TSKgel GMH6-HT × 2 (manufactured by Tosoh Corporation), TSKgel GMH6-HTL × 2 (manufactured by Tosoh Corporation)

[0228] Apparatus: Gel permeation chromatography Alliance GPC2000 (manufactured by Waters Corporation)

[0229] Solvent: o-dichlorobenzene

[0230] Flow rate: 1.0 mL / min

[0231] Sample: 0.15 mg / mL, o-dichlorobenzene solution

[0232] Temperature: 140℃

[0233] Molecular weight conversion: Polyethylene (PE) conversion / Universal calibration method

[0234] In general calibration calculations, the coefficients of the Mark-Houwink viscosity formula shown below are used.

[0235] The coefficient for polystyrene (PS): KPS = 1.38 × 10⁻⁶ -4 aPS = 0.70

[0236] The coefficient for polyethylene (PE): KPE = 5.06 × 10⁻⁶ -4 aPE = 0.70

[0237] The softening point of the low molecular weight olefin polymer (E) is preferably 90°C to 145°C, more preferably 90°C to 135°C, and even more preferably 100°C to 125°C.

[0238] The softening point of low molecular weight olefin polymers (E) was determined according to JIS K2207.

[0239] The density of low molecular weight olefin polymers (E) is not particularly limited, but is preferably 0.890 g / cm³. 3 ~0.980g / cm 3 If the density of the low molecular weight olefin polymer (E) is within the above range, the elongation of the spunbond nonwoven fabric will be even better.

[0240] The density of the low molecular weight olefin polymer (E) is more preferably 0.910 g / cm³. 3 The above is further preferred to be 0.920 g / cm³. 3 above.

[0241] The density of the low molecular weight olefin polymer (E) is more preferably 0.960 g / cm³. 3 The following is a further preferred value: 0.940 g / cm³ 3 the following.

[0242] The density difference between the low molecular weight olefin polymer (E) and the propylene polymer (A) is not particularly limited, but is preferably less than 0.35 g / cm³. 3 More preferably less than 0.20 g / cm³ 3 Further optimization is to select one with a content of less than 0.15 g / cm³. 3 .

[0243] If the difference between the density of the low molecular weight olefin polymer (E) and the density of the propylene polymer (A) is within the above range, the spunbond nonwoven fabric will have better elongation.

[0244] The reasoning is unclear, but it can be considered as follows: If the density of the low molecular weight olefin polymer (E) and the density of the propylene polymer (A) are within the aforementioned range, then it can be considered that, for example, in the propylene polymer (A), polyethylene (D) becomes easier to disperse via the low molecular weight olefin polymer (E). That is, the low molecular weight olefin polymer (E) effectively acts as a compatibilizer for the propylene polymer (A) and polyethylene (D). Therefore, the dispersibility of the propylene polymer (A) and polyethylene (D) is improved. As a result, the elongation of the spunbond nonwoven fabric can be considered improved.

[0245] Low molecular weight olefin polymers (E) are homopolymers of olefins or olefin copolymers composed of two or more olefins.

[0246] Among them, the low molecular weight olefin polymer (E) can be ethylene and α-olefin with 3 to 20 carbon atoms.

[0247] The α-olefin preferably has 3 to 8 carbon atoms, more preferably 3 or 4.

[0248] If the number of carbon atoms in the α-olefin falls within the aforementioned range, the elongation and spinnability of the spunbond nonwoven fabric are further improved. The reason for this is not yet clear, but it can be considered as follows.

[0249] If the number of carbon atoms in the α-olefin is within the above-mentioned range, it can be considered that, for example, in a propylene polymer (A), polyethylene (D) becomes easier to disperse via a low molecular weight olefin polymer (E). That is, the low molecular weight olefin polymer (E) acts as a compatibilizer between the propylene polymer (A) and polyethylene (D). Therefore, the uniformity of the propylene polymer (A) and polyethylene (D) is improved. As a result, properties such as elongation of the spunbond nonwoven fabric can be considered to be improved.

[0250] Low molecular weight olefin polymers (E) can be used in resin compositions in one or in combination of two or more.

[0251] The manufacturing method for low molecular weight olefin polymers (E) is not particularly limited; for example, a first manufacturing method, a second manufacturing method, etc., can be cited. The first manufacturing method refers to a commonly used manufacturing method based on the polymerization of low molecular weight polymers. The second manufacturing method refers to a method that reduces the molecular weight by thermally degrading high molecular weight ethylene polymers.

[0252] Low molecular weight olefin polymers (E) can be purified by methods such as solvent fractionation or distillation, which utilize differences in solubility in solvents.

[0253] As a first manufacturing method, examples include manufacturing methods using Ziegler-Natta catalysts or metallocene catalysts. As manufacturing methods using metallocene catalysts, examples include those described in Japanese Patent Application Publication No. 08-239414 and International Publication No. 2007 / 114102.

[0254] Low molecular weight olefin polymers (E) are commercially available products. Examples of commercially available low molecular weight olefin polymers (E) include "HI-WAX 320P", "EXCEREX 30200B", "HI-WAX 100P", and "HI-WAX 110P" manufactured by Mitsui Chemicals Co., Ltd.

[0255] The content of low molecular weight olefin polymer (E) relative to the total amount of the resin composition is preferably 0.1% to 5.0% by mass.

[0256] From the viewpoint that a sufficient amount of low molecular weight olefin polymer (E) is present at the interface between the marine and island phases in order to improve the dispersibility of propylene polymer (A) and polyethylene (D), the content of low molecular weight olefin polymer (E) is more preferably 0.2% by mass or more, further preferably 1.0% by mass or more, and particularly preferably 1.5% by mass or more, relative to the total amount of the resin composition.

[0257] From the viewpoint of suppressing the reduction in fiber strength, the content of low molecular weight olefin polymer (E) relative to the total amount of the resin composition is more preferably 4.0% by mass or less, further preferably 3.0% by mass or less, and particularly preferably 2.5% by mass or less.

[0258] (1.1.2.6) Other polymers (F)

[0259] From the viewpoint of improving the elongation properties of fibers, the resin composition may contain other polymers (F). Other polymers (F) refer to polymers that are different from propylene polymers (A), thermoplastic polyurethane elastomers (B), polymers (C), polyethylene (D), and low molecular weight olefin polymers (E).

[0260] Other polymers (F) are not particularly limited, for example, the polymer shown below (F1) (hereinafter also referred to as "polymer (F1)"), the polymer shown below (F2) (hereinafter also referred to as "polymer (F2)"), etc.

[0261] (F1): A random copolymer of propylene and at least one selected from ethylene and α-olefins having 4 to 20 carbon atoms.

[0262] (F2): Propylene homopolymers that satisfy (a) to (f) below and have a melting point (Tm) of less than 120°C.

[0263] (a) [mmmm] = 20 mol% ~ 60 mol%

[0264] (b)[rrrr] / (1-[mmmm])≤0.1

[0265] (c) [rmrm] > 2.5 mol%

[0266] (d)[mm]×[rr] / [mr] 2 ≤2.0

[0267] (e) Weight-average molecular weight (Mw) = 10,000–200,000

[0268] (f) Molecular weight distribution (Mw / Mn) < 4

[0269] In (a) to (d), [mmmm] is the proportion of meso-five-unit components, [rrrr] is the proportion of exo-five-unit components, [rmrm] is the proportion of exo- and meso- and exo- and meso-five-unit components, and [mm], [rr] and [mr] are the proportions of three-unit components, respectively.

[0270] (1.1.2.6.1) Polymer (F1)

[0271] Polymer (F1) is a random copolymer comprising units derived from propylene and units derived from at least one α-olefin selected from ethylene and α-olefins having 4 to 20 carbon atoms. Because polymer (F1) is a random copolymer, the resulting spunbond nonwoven fabric tends to have improved softness without producing a sticky feel.

[0272] As a polymer (F1), there are no particular limitations as long as it is a random copolymer containing the above-mentioned constituent units.

[0273] Examples of constituent units that can copolymerize with propylene include: constituent units derived from ethylene; and constituent units derived from α-olefins selected from α-olefins having 4 or more carbon atoms, such as 1-butene, 1-pentene, 1-hexene, 1-octene, 3-methyl-1-butene, 3-methyl-1-pentene, 3-ethyl-1-pentene, 4-methyl-1-pentene, and 4-methyl-1-hexene. Preferably, constituent units derived from ethylene and constituent units derived from α-olefins having 4 to 8 carbon atoms are preferred.

[0274] The polymer (F1) may contain only one type of α-olefin-derived building block or a combination of two or more.

[0275] As polymers (F1), examples include propylene-1-butene random copolymers, propylene-ethylene random copolymers, and propylene-ethylene-1-butene random copolymers.

[0276] Of all the constituent units contained in the polymer (F1), the total proportion of constituent units derived from propylene and constituent units derived from the aforementioned α-olefins other than propylene, such as ethylene, is preferably 80 mol% or more, more preferably 85 mol% or more, and even more preferably 90 mol% or more.

[0277] The melting point (Tm) of the polymer (F1) is preferably 100°C or higher, more preferably 130°C or higher, and even more preferably 150°C or higher.

[0278] The melting point (Tm) of polymer (F1) is defined as the peak observed on the highest temperature side of the melting endothermic curve obtained by using a differential scanning calorimeter (DSC) under a nitrogen atmosphere at -40°C for 5 minutes, followed by heating at 10°C / min. Specifically, it can be determined using a differential scanning calorimeter (Perkin Elmer, DSC-7), by holding a 5 mg sample at -40°C under a nitrogen atmosphere for 5 minutes, followed by heating at 10°C / min, and using the peak observed on the highest temperature side of the resulting melting endothermic curve.

[0279] The crystallinity of the polymer (F1) is preferably 15% or less, more preferably 10% or less, and even more preferably 8% or less.

[0280] The crystallinity of polymer (F1) was calculated from the heat of fusion of the main component in the melting endothermic curve obtained by differential scanning calorimetry (DSC) under a nitrogen atmosphere at -40°C for 5 minutes, followed by heating at 10°C / min. Specifically, a differential scanning calorimeter (Perkin Elmer, DSC-7) was used. A 5 mg sample was held at -40°C under a nitrogen atmosphere for 5 minutes, followed by heating at 10°C / min. The heat of fusion of the main component in the resulting melting endothermic curve was calculated using the following formula.

[0281] Crystallinity = (ΔH / ΔH0) × 100 (%)

[0282] In the formula, ΔH is the heat of fusion (J / g) obtained from the heat of fusion curve of the main component derived from the polymer (F1), and ΔH0 is the heat of fusion (J / g) of the complete crystal of the main component. That is, when the main component is ethylene, ΔH0 is 293 J / g, and when the main component is propylene, ΔH0 is 210 J / g.

[0283] The tensile modulus of the polymer (F1) is preferably 100 MPa or less, more preferably 40 MPa or less, and even more preferably 25 MPa or less.

[0284] The tensile modulus of elasticity of polymer (F1) was determined according to the method of JIS K 7161 (referred to as JIS K 7161-1:2014, corresponding to ISO 527-1:2012).

[0285] From the viewpoint of obtaining good spinnability and excellent stretching processing adaptability, the melt flow rate of polymer (F1) is preferably 1 g / 10 min to 100 g / 10 min, more preferably 5 g / 10 min to 100 g / 10 min, and even more preferably 30 g / 10 min to 70 g / 10 min.

[0286] The melt flow rate of polymer (F1) was determined according to ASTM standard D-1238. The melt flow rate of polymer (F1) was determined under the following conditions: 230°C and a load of 2.16 kg.

[0287] The ratio of the weight-average molecular weight (Mw) to the number-average molecular weight (Mn) of the polymer (F1) (Mw / Mn) (molecular weight distribution) is preferably 1.5 to 5.0, and more preferably 1.5 to 3.0 from the perspective of obtaining fibers with better spinnability and particularly excellent fiber strength.

[0288] The Mw and Mn of polymer (F1) can be determined by GPC (gel permeation chromatography) using the method described later.

[0289] (1.1.2.6.2) Polymer (F2)

[0290] The polymer (F2) is a propylene homopolymer with a melting point (Tm) of less than 120°C that satisfies the following (a) to (f).

[0291] (1.1.2.6.2.1)[mmmm]

[0292] The polymer (F2) satisfies the following equation (a).

[0293] Formula (a): [mmmm] = 20 mol% ~ 60 mol%

[0294] If the meso-pentameric component percentage [mmmm] of the polymer (F2) is above 20 mol%, the stickiness will be suppressed; if it is below 60 mol%, the crystallinity will not become too high, thus improving the elastic recovery.

[0295] The meso-five-unit component percentage [mmmm] of polymer (F2) is preferably 30 mol% to 50 mol%, more preferably 40 mol% to 50 mol%.

[0296] The proportions of meso-pentameric components [mmmm], the proportions of racemic pentameric components [rrrr] (described later), and the proportions of racemic-mesomeric-mesomeric pentameric components [rmrm] are based on the method proposed by A. Zambelli et al. in "Macromolecules", 6, 925 (1973), utilizing... 13 The C-NMR spectrum is used to determine the methyl signal and the racemic, racemic, and racemic-mesotropic fractions in the polypropylene molecular chain, expressed in pentamelidic units. A larger pentamelidic unit fraction [mmmm] indicates higher stereoregularity. The ternary unit fractions [mm], [rr], and [mr], described later, are also calculated using the same method.

[0297] It should be noted that, 13 The C-NMR spectrum determination can be performed based on the peak assignment proposed by A. Zambelli et al. in "Macromolecules", 8, 687 (1975) and using the following apparatus and conditions.

[0298] [Apparatus and Conditions]

[0299] Device: JNM-EX400 model manufactured by Nippon Electronics Co., Ltd. 13 C-NMR device

[0300] Method: Proton complete decoupling

[0301] Concentration: 220 mg / mL

[0302] Solvent: A 90:10 (volume ratio) mixture of 1,2,4-trichlorobenzene and deuterated benzene.

[0303] Temperature: 130℃

[0304] Pulse width: 45°

[0305] Pulse repetition time: 4 seconds

[0306] Total: 10,000 times

[0307] [Calculation formula]

[0308] M = m / S × 100

[0309] R = γ / S × 100

[0310] S=Pββ+Pαβ+Pαγ

[0311] S: Signal intensity of the methyl carbon atom in the side chain of all propylene units

[0312] Pββ: 19.8ppm~22.5ppm

[0313] Pαβ: 18.0ppm~17.5ppm

[0314] Pαγ: 17.5ppm~17.1ppm

[0315] γ: Racemic five-unit chain: 20.7ppm~20.3ppm

[0316] m: Meso-racic five-unit chain: 21.7ppm~22.5ppm

[0317] (1.1.2.6.2.2)[rrrr] / (1-[mmmm])

[0318] The polymer (F2) satisfies the following equation (b).

[0319] Equation (b): [rrrr] / (1-[mmmm])≤0.1

[0320] The value of [rrrr] / [1-mmmm] is derived from the fraction of the five-unit group mentioned above and is an indicator of the uniformity of the regularity distribution of the propylene-derived constituent units in the polymer (F2). If this value increases, it becomes a mixture of highly regular polypropylene and atactic polypropylene, as is the case with conventional polypropylene manufactured using existing catalyst systems, resulting in stickiness.

[0321] In polymer (F2), if [rrrr] / (1-[mmmm]) is less than 0.1, the stickiness in the obtained spunbond nonwoven fabric will be suppressed.

[0322] From this perspective, [rrrr] / (1-[mmmm]) is preferably 0.05 or less, and more preferably 0.04 or less.

[0323] (1.1.2.6.2.3)[rmrm]

[0324] The polymer (F2) satisfies the following equation (c).

[0325] Formula (c): [rmrm] > 2.5 mol%

[0326] If the racemic and meso-racemic fractions [rmrm] of polymer (F2) are greater than 2.5 mol%, the randomness of polymer (F2) increases, and the elastic recovery of spunbond nonwoven fabric is further improved.

[0327] The racemic and meso-racemic fractions [rmrm] of the polymer (F2) are preferably 2.6 mol% to 10 mol%, more preferably 2.7 mol% to 10 mol%.

[0328] (1.1.2.6.2.4)[mm]×[rr] / [mr] 2

[0329] The polymer (F2) satisfies the following equation (d).

[0330] Formula (d): [mm]×[rr] / [mr] 2 ≤2.0

[0331] [mm]×[rr] / [mr] 2 This is an indicator of the randomness of the polymer (F2). A value below 2.0 indicates a spunbond nonwoven fabric with sufficient elastic recovery, and tacky properties are suppressed. [mm]×[rr] / [mr] 2 The closer it gets to 0.25, the higher the randomness becomes.

[0332] From the perspective of achieving sufficient elastic recovery as described above, [mm]×[rr] / [mr] 2 Preferably, the value is greater than 0.25 and less than 1.8, and more preferably 0.5 to 1.5.

[0333] (1.1.2.6.2.5) Weight-average molecular weight (Mw)

[0334] The polymer (F2) satisfies the following equation (e).

[0335] Formula (e): Weight-average molecular weight (Mw) = 10,000–200,000

[0336] For polymer (F2) as a propylene homopolymer, if the weight-average molecular weight is 10,000 or higher, the viscosity of polymer (F2) is moderate and not too low, thus suppressing filament breakage when manufacturing spunbond nonwoven fabrics obtained from the resin composition. If the weight-average molecular weight is 200,000 or lower, the viscosity of polymer (F2) is not too high, and the spinnability is improved.

[0337] The weight-average molecular weight of polymer (F2) is preferably 30,000 to 150,000, more preferably 50,000 to 150,000. The method for determining the weight-average molecular weight of polymer (F2) will be described later.

[0338] (1.1.2.6.2.6) Molecular weight distribution (Mw / Mn)

[0339] The polymer (F2) satisfies the following equation (f).

[0340] Equation (f): (f) Molecular weight distribution (Mw / Mn) < 4

[0341] In polymer (F2), if the molecular weight distribution (Mw / Mn) is less than 4, it will inhibit the stickiness of the obtained spunbond nonwoven fabric.

[0342] The molecular weight distribution of the polymer (F2) is preferably 3 or less.

[0343] In polymers (F1) and (F2), the weight-average molecular weight (Mw) is the weight-average molecular weight converted from that of polystyrene, determined by gel permeation chromatography (GPC) using the apparatus and conditions described below. The molecular weight distribution (Mw / Mn) described above is a value calculated from the number-average molecular weight (Mn) determined in the same manner and the weight-average molecular weight (Mw) described above.

[0344] [Measurement Conditions]

[0345] Column: TOSO GMHHR-H(S)HT

[0346] Detector: Waters 150C RI detector for liquid chromatography

[0347] Solvent: 1,2,4-trichlorobenzene

[0348] Measurement temperature: 145℃

[0349] Flow rate: 1.0 mL / min

[0350] Sample concentration: 2.2 mg / mL

[0351] Injection volume: 160 μL

[0352] Standard Curve: Universal Calibration

[0353] Parser: HT-GPC (version 1.0)

[0354] (1.1.2.6.2.7) Melting point (Tm-D)

[0355] The polymer (F2) preferably satisfies the following formula (g).

[0356] Formula (g): Melting point (Tm-D) = 0℃~120℃

[0357] If the melting point (Tm-D) of the polymer (F2) is above 0°C, it will suppress the stickiness of the spunbond nonwoven fabric formed from the resin composition; if it is below 120°C, sufficient elastic recovery can be obtained.

[0358] From this perspective, the melting point (Tm-D) is preferably 0℃~100℃, and more preferably 30℃~100℃.

[0359] The melting point (Tm-D) of the polymer (F2) can be determined by taking the peak of the highest temperature side from the melting endothermic curve obtained by using a differential scanning calorimeter (Perkin Elmer, DSC-7), which is obtained by holding a 10 mg sample at -10 °C for 5 minutes in a nitrogen atmosphere and then heating it at 10 °C / min.

[0360] (1.1.2.6.2.8) Melt flow rate

[0361] From the viewpoint of obtaining good spinnability and excellent adaptability to stretching, the melt flow rate of polymer (F2) is preferably 1 g / 10 min to 100 g / 10 min, more preferably 5 g / 10 min to 100 g / 10 min, and even more preferably 30 g / 10 min to 70 g / 10 min.

[0362] The melt flow rate of polymer (F2) was determined according to ASTM standard D-1238. The melt flow rate of polymer (F2) was determined under the following conditions: 230°C and a load of 2.16 kg.

[0363] The polymer (F2) can be synthesized, for example, using a homogeneous system catalyst known as a metallocene catalyst, as described in International Publication No. 2003 / 087172.

[0364] When the resin composition and the fiber contain at least one of polymer (F1) and polymer (F2), the content of polymer (F1) and polymer (F2) is preferably 5% to 30% by mass, more preferably 10% to 25% by mass, relative to the total amount of the resin composition.

[0365] (1.1.2.7) Additives (G)

[0366] The resin composition may contain additives (G) within the scope of achieving the effects of this disclosure. Examples of additives (G) include antioxidants, weather stabilizers, light stabilizers, antistatic agents, slip agents, hydrophilic agents, antifogging agents, antiblocking agents, lubricants, nucleating agents, dyes, pigments, natural oils, synthetic oils, waxes, and amide compounds. Only one of these additives (G) may be used in the resin composition, or two or more may be used in combination.

[0367] The resin composition may contain an amide compound. The amide compound can function as a lubricant. Examples of amide compounds include fatty acid amides (e.g., fatty acid amides with 15 to 22 carbon atoms). It is believed that by adsorbing fatty acid amides with 15 to 22 carbon atoms onto the fiber surface of spunbond nonwoven fabrics, the fiber surface is modified, resulting in improved softness, feel, and anti-adhesion properties, and more effectively inhibiting the adhesion of fibers to components of various rotating equipment used in embossing processes.

[0368] In this disclosure, "the number of carbon atoms in a fatty acid amide" refers to the number of carbon atoms contained in the molecule, and the carbon atoms that form the amide bond are also included in the aforementioned number of carbon atoms.

[0369] The fatty acid amide preferably has 15 to 22 carbon atoms, more preferably 18 to 22. Examples of fatty acid amides include fatty acid monoamide compounds, fatty acid diamide compounds, saturated fatty acid monoamide compounds, and unsaturated fatty acid diamide compounds. Specifically, examples include palmitamide (16 carbon atoms), stearamide (18 carbon atoms), oleamide (18 carbon atoms), and erucamide (22 carbon atoms). Only one of these amide compounds may be used in the resin composition, or two or more may be used in combination.

[0370] When the resin composition contains an amide compound, the content of the amide compound is preferably 0.1% to 5.0% by mass, more preferably 0.1% to 3.0% by mass, and even more preferably 0.1% to 1.0% by mass, relative to the total amount of the resin composition.

[0371] (1.1.3) Physical properties of spunbond nonwoven fabrics

[0372] The preferred air permeability of spunbond nonwoven fabric is 280 cm⁻¹. 3 / cm 2 • seconds or more, and the strength index (N / 25mm) relative to the apparent weight (g / m²) 2 The ratio of strength index to surface strength (hereinafter also referred to as "ratio (strength index / finishing weight)") is 0.70 [(N / 25mm) / (g / m²)]. 2 )〕above.

[0373] The air permeability, strength index, and mesh size were measured using the same methods as described in the examples.

[0374] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, a more preferable ratio is 0.70 [(N / 25mm) / (g / m²)]. 2 )〕~2.0〔(N / 25mm) / (g / m 2)〕, further preferably 0.72〔(N / 25mm) / (g / m 2 )〕~1.7〔(N / 25mm) / (g / m 2 )〕, particularly preferably 0.74〔(N / 25mm) / (g / m 2 )〕~1.5〔(N / 25mm) / (g / m 2 )〕.

[0375] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the preferred air permeability of spunbond nonwoven fabrics is 280 cm⁻¹. 3 / cm 2 ·seconds ~1000cm 3 / cm 2 • seconds, preferably 290 cm 3 / cm 2 ·seconds ~ 800cm 3 / cm 2 • seconds, further optimized to 300cm 3 / cm 2 ·seconds ~600cm 3 / cm 2 • seconds, preferably 310cm 3 / cm 2 ·seconds ~ 550cm 3 / cm 2 ·Second.

[0376] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabric, the strength index of spunbond nonwoven fabric is preferably 15 (N / 25mm) to 40 (N / 25mm), more preferably 18 (N / 25mm) to 35 (N / 25mm), and even more preferably 20 (N / 25mm) to 30 (N / 25mm).

[0377] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the preferred mesh size for spunbond nonwoven fabrics is 1 g / m². 2 ~100g / m 2 More preferably 5g / m 2 ~80g / m 2 Further preferred is 10g / m 2 ~70g / m 2 .

[0378] (1.1.4) Composition of spunbond nonwoven fabric

[0379] Spunbond nonwoven fabrics can be spunbond nonwoven fabrics consisting of a single layer containing island fibers, or nonwoven fabric laminates consisting of two or more layers of spunbond nonwoven fabrics containing island fibers, or nonwoven fabric laminates consisting of spunbond nonwoven fabrics consisting only of island fibers and other layers besides the spunbond nonwoven fabrics. The other layers besides the spunbond nonwoven fabrics can be one layer or two or more layers.

[0380] Other layers besides spunbond nonwovens include knitted fabrics, woven fabrics, spunbond nonwovens other than those without island fibers (hereinafter also referred to as "other nonwovens"), and films. The aforementioned nonwovens can be cited as examples of other nonwovens.

[0381] There are no particular limitations on the methods for forming nonwoven fabric laminates. Examples include hot embossing, ultrasonic welding and other hot fusion methods, needle punching, water spraying and other mechanical interlacing methods, the use of hot melt adhesives, urethane adhesives and other adhesives, extrusion lamination and other methods.

[0382] Preferably, a portion of the spunbond nonwoven fabric is press-bonded (preferably heat-fused).

[0383] As a method for pressing together a part of a spunbond nonwoven fabric, examples include methods using ultrasonic waves, hot embossing using embossing rollers, and hot air penetration.

[0384] Spunbond nonwoven fabrics can have a seamed portion and a non-seamed portion. The area ratio of the seamed portion is preferably 5% to 30%, more preferably 5% to 20%, and even more preferably 8% to 19%. This allows for a good balance between the softness and strength of the spunbond nonwoven fabric, etc.

[0385] The area ratio of the crimped portion is defined as the ratio of the area of ​​the crimped portion to the area of ​​the observed spunbond nonwoven fabric when a 10mm × 10mm test piece is taken from the spunbond nonwoven fabric and observed using an electron microscope (magnification: 100x) on the contact surface between the test piece and the embossing roller. The area ratio of the protrusion formed on the embossing roller that forms the crimped portion is also called the "embossing area ratio". The preferred range of the embossing area ratio is the same as the preferred range of the area ratio of the crimped portion described above.

[0386] Examples of shapes that can be used for the press-fitting part include circles, ovals, oblongs, squares, rhombuses, rectangles, quadrilaterals, and continuous shapes based on these shapes.

[0387] (1.1.5) Applications of spunbond nonwoven fabrics

[0388] Spunbond nonwovens have higher air permeability than other nonwovens of the same strength. Therefore, spunbond nonwovens are suitable for applications requiring high air permeability and other properties.

[0389] The applications of spunbond nonwovens are not particularly limited and can be widely used in common applications where spunbond nonwovens are commonly used. Examples of applications for spunbond nonwovens include filters, sanitary materials, medical components, packaging materials (oxygen absorbers, heat packs, hot compresses, food packaging materials, etc.), battery separators, thermal insulation materials, heat insulation materials, protective clothing, clothing components, electronic materials, and sound-absorbing materials. Spunbond nonwovens are preferably used as sanitary materials.

[0390] (1.2) Sanitary materials

[0391] The first type of sanitary material includes the spunbond nonwoven fabric of the first type. Examples of sanitary materials include, for example: absorbent items such as disposable diapers, disposable underwear, sanitary products, absorbent pads, and pet pads; medical sanitary materials such as bandages, medical gauze, towels, bed sheets, and wet dressings; and industrial masks and sanitary masks.

[0392] The sanitary material is not limited to this and can also be suitably used for other sanitary material applications. The sanitary material may comprise a nonwoven fabric laminate consisting of two or more layers of spunbond nonwoven fabric of the first type, or it may comprise a nonwoven fabric laminate having a spunbond nonwoven fabric of the first type and other layers besides the nonwoven fabric of the first type.

[0393] (1.3) Manufacturing method of spunbond nonwoven fabric

[0394] In the first method for manufacturing spunbond nonwoven fabric, a resin composition is melt-spun to form a continuous fiber assembly, and the continuous fiber assembly is stretched using cooling air. The resin composition comprises a propylene polymer (A), a thermoplastic polyurethane elastomer (B), and a polymer (C) modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups. The air velocity of the cooling air (hereinafter also referred to as "stretching air velocity") is 3000 m / min or higher.

[0395] In the first method of manufacturing spunbond nonwoven fabric, a continuous fiber assembly is introduced into the interior of the stretching section, and stretching is performed using cooling air. The term "stretching air velocity" refers to the flow rate of the cooling air (Nm³). 3 / minute) relative to the narrowest part of the diameter of the stretching section (e.g., neck 16a described later) cross-sectional area (m²) 2 The ratio of ).

[0396] The manufacturing method of the spunbond nonwoven fabric of the first embodiment has the above-described structure, and thus the spunbond nonwoven fabric of the first embodiment can be obtained.

[0397] This effect is speculated to be based on the following reasons, but is not limited to these.

[0398] In the first method, the stretching air velocity is above 3000 m / min. That is, the continuous fiber group is subjected to strong stretching. Therefore, it is inferred that a spunbond nonwoven fabric with a peak intensity / crystallinity ratio within the above range can be obtained.

[0399] In detail, the first type of spunbond nonwoven fabric uses a resin composition as a raw material, and is manufactured, for example, in the following manner: The resin composition is fed into an extruder and melted. The melt of the resin composition is spun using a spunbond nonwoven fabric forming machine with multiple spinnerets. The airflow is controlled using a blower or the like, and the resulting continuous fiber assembly is stretched. At this time, the continuous fiber assembly is cooled as needed. Then, the continuous fiber assembly is piled on the collecting surface of the spunbond nonwoven fabric forming machine, thereby obtaining a spunbond web. The obtained spunbond web is heated and pressurized using an embossing roller. Thus, a spunbond nonwoven fabric is obtained.

[0400] (1.3.1) An example of a method for manufacturing spunbond nonwoven fabrics

[0401] The following is for reference Figure 1 Here is a detailed description of an example of a method for manufacturing spunbond nonwoven fabric according to the first method. In the closed-loop spunbond process, a continuous fiber assembly formed by melt spinning a resin composition is cooled and stretched in a closed space.

[0402] Figure 1 The closed-loop spunbond manufacturing apparatus 100 shown includes a spinning section 10. The spinning section 10 includes an extruder 11, a spinneret 12, a cooling chamber 13, a cooling air supply section 14, a cooling air supply section 15, and a stretching section 16. The extruder 11 extrudes a resin composition. The spinneret 12 spins the molten resin composition into fibers. The cooling chamber 13 cools the continuous fiber assembly 1 spun from the spinneret 12. The cooling air supply sections 14 and 15 supply cooling air A to the cooling chamber 13 and the stretching section 16. The stretching section 16 stretches the continuous fiber assembly 1.

[0403] First, the resin composition is fed into the extruder 11. The resin composition fed into the extruder 11 is melt-mixed within the extruder 11. The melt of the resin composition is extruded from the extruder 11.

[0404] The molten resin composition extruded from the extruder 11 is introduced into the spinneret 12. The molten resin composition introduced into the spinneret 12 is extruded from the spinneret 12 and spun. Thus, a continuous fiber assembly 1 is formed.

[0405] The continuous fiber assembly 1 is introduced into the cooling chamber 13. The continuous fiber assembly 1 introduced into the cooling chamber 13 is cooled by cooling air A. Cooling air A is supplied from at least one of cooling air supply unit 14 and cooling air supply unit 15 into the cooling chamber 13 and the stretching section 16. The cooled continuous fiber assembly 1 is then introduced into the stretching section 16, which is located on the downstream side of the cooling chamber 13.

[0406] The stretching portion 16 has a neck 16a and a cylindrical portion 16b. The cylindrical portion 16b is formed at the lower end (i.e., the side of the moving trapping member 21) of the neck 16a in the vertical direction (i.e., the direction of gravity). The neck 16a is bottleneck-shaped. The cylindrical portion 16b is cylindrical. The hollow portion of the cylindrical portion 16b is as follows: Figure 1 As shown, it extends downwards. The continuous fiber bundle 1 introduced into the stretching section 16 is stretched by the increased speed of the cooling air at the neck 16a. The stretched continuous fiber bundle 1, passing through the cylinder section 16b, is dispersed and captured on the movable capturing member 21.

[0407] The dispersed continuous fiber group 1 is efficiently captured on the movable capturing member 21 by the attraction unit 22. The attraction unit 22 is disposed on the lower part of the capturing surface of the movable capturing member 21. Thus, a spunbond web 2 is formed.

[0408] Then, the fibers contained in the spunbond web 2 are bonded together, for example, by heating and pressing an embossing roller (not shown). Thus, a spunbond nonwoven fabric is obtained.

[0409] There are no particular limitations on the melting temperature of the resin composition, as long as it is above the softening temperature or melting temperature of the resin composition and below the thermal decomposition temperature of the resin composition. It can be appropriately set according to the physical properties of the resin composition.

[0410] The temperature of the spinneret 12 can be appropriately adjusted according to the properties of the resin composition. Considering the properties of the propylene polymer (A) contained in the resin composition, the temperature of the spinneret 12 is preferably 180°C to 240°C, more preferably 190°C to 230°C, and even more preferably 200°C to 225°C.

[0411] The orifice diameter of the spinneret 12 is not particularly limited, but from the viewpoint of the elongation of spunbond nonwoven fabric, it is preferably 0.05 mm to 1.00 mm.

[0412] From the viewpoint of the elongation of spunbond nonwoven fabric, the single-hole discharge rate of the molten resin composition from the spinneret 12 is preferably 0.1 g / min to 3.0 g / min, more preferably 0.3 g / min to 1.0 g / min.

[0413] The temperature of the cooling air A that cools the continuous fiber assembly extruded from the spinneret 12 is not particularly limited as long as it is the temperature at which the resin composition cures. The temperature of the cooling air A is preferably 5°C to 50°C, more preferably 10°C to 40°C, and even more preferably 15°C to 30°C.

[0414] Cooling air volume per 1m width (m³) 3 The ratio of ( / minute / m) to the single-orifice discharge rate (m) 2 / g) There are no particular restrictions, but 1m is preferred. 2 / g~10000m 2 / g, preferably 10m 2 / g~1000m 2 / g.

[0415] The stretching air velocity is above 3,000 m / min.

[0416] From the perspective of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the stretching air velocity is preferably 3,200 m / min or more, more preferably 3,500 m / min or more, and even more preferably 3,800 m / min or more.

[0417] There are no particular restrictions on the stretching air velocity; for example, it can be below 6,000 m / min or below 5,500 m / min.

[0418] Regarding the flow rate of cooling air A supplied from cooling air supply unit 14 and cooling air supply unit 15 respectively, as well as the cross-sectional area of ​​neck 16a, there are no particular restrictions as long as the stretching air velocity is within the above range, and it can be appropriately set in order to make the stretching air velocity a specific range.

[0419] In the first method of manufacturing spunbond nonwoven fabric, a portion of the fibers contained in the spunbond nonwoven fabric can be thermally bonded. The fibers contained in the spunbond nonwoven fabric can be pre-compacted using rollers before thermal bonding.

[0420] The method for manufacturing spunbond nonwoven fabric as a first approach has been described using a closed-loop spunbond method as an example; however, the method for manufacturing spunbond nonwoven fabric disclosed herein is not limited to a closed-loop spunbond method. The method for manufacturing spunbond nonwoven fabric disclosed herein can also be an open-loop spunbond method. In the open-loop spunbond method, the continuous fiber assembly formed by melt spinning a resin composition is cooled.

[0421] (2) Second method

[0422] (2.1) Spunbond nonwoven fabric

[0423] The second type of spunbond nonwoven fabric comprises fibers formed from a resin composition. The resin composition comprises an acrylic polymer (A), a nucleating agent (b), and a polymer (C) modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups. The fibers have an island structure. The sea phase contained in the island structure comprises the acrylic polymer (A). The island phase contained in the island structure comprises the nucleating agent (b). The ratio of the peak intensity of the α-crystal of the fibers to the crystallinity of the fibers is 10.5 or less [intensity [count] / %]. The peak intensity of the α-crystal represents the peak intensity of the (110) plane of the acrylic polymer (A) near 2θ = 14° in an X-ray diffraction pattern measured using an X-ray diffraction apparatus using CuKα rays.

[0424] In this disclosure, the term "crystallizing nucleating agent" refers to a substance that promotes the crystallization of thermoplastic resins in the field of thermoplastic resins.

[0425] The spunbond nonwoven fabric of the second type, due to its aforementioned structure, exhibits excellent tensile strength and high air permeability. In other words, the spunbond nonwoven fabric of the second type achieves the effect of balancing the usually trade-off between maintaining or increasing tensile strength and improving air permeability.

[0426] (2.1.1) Fiber

[0427] The second type of spunbond nonwoven fabric contains fibers.

[0428] (2.1.1.1) Ratio (peak intensity / crystallinity)

[0429] The peak intensity / crystallinity ratio is 10.5 or less [intensity [count] / %]. The peak intensity / crystallinity ratio is the same as that of the first method.

[0430] (2.1.1.2) Island structure

[0431] In the second method, the fiber has an island structure.

[0432] In the second embodiment, the island-island fiber is formed from a resin composition. The resin composition comprises a propylene polymer (A), a crystallizing nucleating agent (b), and a polymer (C), and may further comprise polyethylene (D) if desired.

[0433] Details of the resin composition will be described later.

[0434] Island structures have marine facies and multiple island facies. Multiple island facies exist (e.g., dispersed) within the marine facies.

[0435] The marine phase comprises a propylene polymer (A), and the plurality of island phases each comprise a nucleating agent (b). When the resin composition further comprises polyethylene (D), it is preferable that the marine phase comprises a propylene polymer (A), and the plurality of island phases each comprise an island phase of the nucleating agent (b) and an island phase of polyethylene (D).

[0436] The fiber diameter of the island-island fiber is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 28 μm or less. The smaller the fiber diameter, the better the softness of the nonwoven fabric. From an operational point of view, the fiber diameter of the island-island fiber is preferably 10 μm or more. The island-island fiber can be long fibers (staples) or single fibers (filaments). Furthermore, there are no particular limitations on the cross-sectional shape of the island-island fiber; for example, circular, elliptical, and irregular cross-sections are possible.

[0437] (2.1.1.2.1) Island phase of nucleating agent (b)

[0438] Using a transmission electron microscope at 25.5 μm 2 When observing a cross-section orthogonal to the fiber axis in the field of view, it is preferable that the average diameter of the island phase containing the nucleating agent (b) is less than 0.095 μm, and the number of island phases containing the nucleating agent (b) is more than 200. This improves spinnability while maintaining the tensile strength and air permeability of the spunbond nonwoven fabric.

[0439] There is no particular limitation on the magnification of a transmission electron microscope (TEM), which can be appropriately adjusted to the extent that the size and number of island phases in the fiber cross-section can be determined. For example, the magnification of a TEM can be 40,000x.

[0440] The methods for determining the average diameter of the island phase containing the nucleating agent (b) and the number of island phases containing the nucleating agent (b) are the same as those described in the examples.

[0441] The average diameter of the island phase containing the nucleating agent (b) is the same as the average diameter exemplified in the first embodiment as the average diameter of the island phase containing the thermoplastic polyurethane elastomer (B).

[0442] The number of island phases containing the nucleating agent (b) is the same as the number of island phases exemplified in the first embodiment as the number of island phases containing the thermoplastic polyurethane elastomer (B).

[0443] The ratio of the island phase area to the total cross-sectional area of ​​the island-island fiber (hereinafter referred to as the "island phase area ratio") is preferably 1.0% or more. With an island phase area ratio of 1.0% or more, the orientation crystallization of the propylene polymer (A) within the island-island fiber is easily hindered.

[0444] The island phase area ratio is preferably below 20%. If the island phase area ratio is below 20%, the orientation crystallization of the propylene polymer (A) within the island-island fiber is easily hindered. As a result, the spunbond nonwoven fabric exhibits superior elongation and spinnability.

[0445] There are no particular limitations on the methods for adjusting the island phase area ratio; examples include the raw material adjustment method.

[0446] (2.1.1.2.2) Island phase of polyethylene (D)

[0447] When the resin composition further comprises polyethylene (D), the sample was analyzed using a transmission electron microscope at 25.5 μm. 2 When observing a cross section orthogonal to the fiber axis in the field of view, it is preferable that the average diameter of the island phase containing polyethylene (D) is 0.11 μm or less, and the number of island phases containing polyethylene (D) is 150 or more.

[0448] There is no particular limitation on the magnification of a transmission electron microscope (TEM), which can be appropriately adjusted to the extent that the size and number of island phases in the fiber cross-section can be determined. For example, the magnification of a TEM can be 40,000x.

[0449] The island phase of polyethylene (D) is the same as the island phase exemplified as the island phase of polyethylene (D) in the first embodiment.

[0450] (2.1.1.3) Morphology, etc.

[0451] The morphology of the fibers contained in the spunbond nonwoven fabric is the same as that exemplified in the first embodiment as the morphology of the fibers contained in the spunbond nonwoven fabric.

[0452] (2.1.2) Resin Composition

[0453] The fibers are formed from a resin composition.

[0454] The resin composition comprises an propylene polymer (A), a nucleating agent (b), and a polymer (C). Details of each of the propylene polymer (A), nucleating agent (b), and polymer (C) will be described later.

[0455] (2.1.2.1) Propylene polymers (A)

[0456] The resin composition comprises an propylene polymer (A).

[0457] The propylene polymer (A) is the same as the propylene polymer exemplified as propylene polymer (A) in the first embodiment.

[0458] (2.1.2.2) Crystallization nucleating agent (b)

[0459] The resin composition contains a crystallizing nucleating agent (b).

[0460] As a nucleating agent (b), all substances known as nucleating agents in the field of thermoplastic resins can be used, including organic and inorganic nucleating agents.

[0461] In this disclosure, "organic nucleating agent" refers to an organic compound capable of forming a three-dimensional network structure based on self-organization through thermal melting and cooling, or through melt mixing and shear flow. By adding such an organic nucleating agent to a thermoplastic resin and subjecting it to thermal melting and cooling, the growth of fine and uniform crystals in the thermoplastic resin can be promoted.

[0462] Specific examples of organic crystal nucleating agents include thermoplastic polyurethane elastomers (B), sorbitol compounds, phosphate ester compounds, amide compounds, and rosin compounds. Sorbitol compounds include sorbitol compounds containing aromatic rings and sorbitol compounds containing aliphatic rings, with sorbitol compounds containing aromatic rings being preferred.

[0463] Specific examples of inorganic nucleating agents include talc, kaolinite, montmorillonite, synthetic mica, clay, zeolite, silica, graphite, carbon black, zinc oxide, magnesium oxide, titanium oxide, calcium sulfide, boron nitride, calcium carbonate, barium sulfate, aluminum oxide, neodymium oxide, and metal salts of phenylphosphonates. To improve dispersibility in resin compositions, these inorganic nucleating agents are preferably modified with organic compounds.

[0464] The nucleating agent (b) preferably comprises a thermoplastic polyurethane elastomer (B). This results in superior tensile strength and high air permeability in the spunbond nonwoven fabric.

[0465] As a thermoplastic polyurethane elastomer (B), it is the same as the thermoplastic polyurethane elastomer exemplified as a thermoplastic polyurethane elastomer (B) in the first embodiment.

[0466] From the viewpoint of balancing the tensile strength and air permeability of spunbond nonwoven fabrics, the content of the nucleating agent (b) relative to the total amount of the resin composition is preferably 2.0% to 20.0% by mass, more preferably 2.5% to 19.0% by mass, and even more preferably 3.0% to 18.0% by mass.

[0467] The following describes the case where the nucleating agent (b) is a thermoplastic polyurethane elastomer (B) in the second embodiment.

[0468] (2.1.2.3) Polymer (C)

[0469] The resin composition contains a polymer (C).

[0470] The polymer (C) is the same as the polymer exemplified as polymer (C) in the first embodiment.

[0471] (2.1.2.4) Polyethylene (D)

[0472] The resin composition may contain polyethylene (D).

[0473] Polyethylene (D) is the same as the polyethylene exemplified as polyethylene (D) in the first embodiment.

[0474] (2.1.2.5) Low molecular weight olefin polymers (E)

[0475] The resin composition may contain low molecular weight olefin polymers (E).

[0476] The low molecular weight olefin polymer (E) is the same as the low molecular weight olefin polymer (E) exemplified in the first embodiment.

[0477] (2.1.2.6) Other polymers (F)

[0478] From the viewpoint of improving the elongation properties of fibers, the resin composition may contain other polymers (F).

[0479] Other polymers (F) are the same as the other polymers exemplified as other polymers (F) in the first embodiment.

[0480] (2.1.2.7) Additives (G)

[0481] The resin composition may contain additives (G) to the extent that it achieves the effects of this disclosure.

[0482] The additive (G) is the same as the additive (G) exemplified in the first embodiment.

[0483] (2.1.3) Physical properties of spunbond nonwoven fabrics

[0484] The preferred air permeability of spunbond nonwoven fabric is 280 cm⁻¹. 3 / cm 2 • seconds or more, and the strength index (N / 25mm) relative to the apparent weight (g / m²) 2 The ratio of strength index to surface strength (hereinafter also referred to as "ratio (strength index / finishing weight)") is 0.70 [(N / 25mm) / (g / m²)]. 2 )〕above.

[0485] The air permeability, strength index, and mesh size were measured using the same methods as described in the examples.

[0486] The ratio (strength index / spot) is the same as the ratio (strength index / spot) exemplified as the ratio (strength index / spot) in the first method.

[0487] The air permeability of the spunbond nonwoven fabric is the same as that exemplified as air permeability in the first method.

[0488] The strength index of the spunbond nonwoven fabric is the same as the strength index exemplified as the strength index in the first method.

[0489] The patch of the spunbond nonwoven fabric is the same as the patch exemplified as a patch in the first method.

[0490] (2.1.4) Composition of spunbond nonwoven fabric

[0491] The structure of the spunbond nonwoven fabric is the same as that exemplified in the first embodiment as the structure of the spunbond nonwoven fabric.

[0492] (2.1.5) Applications of spunbond nonwoven fabrics

[0493] The uses of spunbond nonwoven fabrics are the same as those exemplified in the first embodiment as uses of spunbond nonwoven fabrics.

[0494] (2.2) Sanitary materials

[0495] The second type of sanitary material comprises the spunbond nonwoven fabric of the second type. The second type of sanitary material comprises the spunbond nonwoven fabric of the second type in place of the spunbond nonwoven fabric of the first type, and is otherwise the same as the sanitary material of the first type.

[0496] (2.3) Manufacturing method of spunbond nonwoven fabric

[0497] In the second method for manufacturing spunbond nonwoven fabric, a resin composition is melt-spun to form a continuous fiber assembly, and the continuous fiber assembly is stretched using cooling air. The resin composition comprises an propylene polymer (A), a nucleating agent (b), and a polymer (C) modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups. The air velocity of the cooling air (hereinafter also referred to as "stretching air velocity") is 3000 m / min or higher.

[0498] The manufacturing method of the second type of spunbond nonwoven fabric has the above-described structure, and thus the second type of spunbond nonwoven fabric can be obtained.

[0499] In the second method of manufacturing spunbond nonwoven fabric, the resin composition contains a crystallizing nucleating agent (b) instead of a thermoplastic polyurethane elastomer (B), otherwise it is the same as the first method of manufacturing spunbond nonwoven fabric.

[0500] Example

[0501] The present disclosure will be further described in detail below based on embodiments, but the present disclosure is not limited to these embodiments. The materials, amounts, proportions, processing order, etc., shown in the following embodiments can be appropriately modified without departing from the spirit of the present disclosure.

[0502] [1] Measurement and evaluation methods

[0503] The physical properties, etc., in the examples and comparative examples were determined and evaluated by the following methods.

[0504] [1.1] Spinning properties

[0505] Based on the spinning results of the spunbond nonwoven fabric shown in the examples, the spinnability is evaluated according to the following criteria. An acceptable evaluation of spinnability is "A".

[0506] A: It can be spun without any problems and can be used to manufacture spunbond nonwoven fabrics.

[0507] B: Spinning itself can be achieved, but there are many broken fibers, making it impossible to manufacture spunbond nonwoven fabrics.

[0508] [1.2] Confirmation of island structure, number of island phases, average diameter of island phases, and area ratio of island phases.

[0509] Fibers were extracted from spunbond nonwoven fabric and embedded in paraffin wax. The test specimen was then placed on a microtome with the blade parallel to the fiber axis, and sliced ​​along a direction orthogonal to the fiber axis. The resulting fiber cross-sections were stained with RuO4 and then sliced ​​again to prepare ultrathin sections. After carbon reinforcement, the stained cross-sections were observed using a transmission electron microscope (TEM). Island structures were observed within the fiber cross-sections. It should be noted that island phases stained black, either entirely or peripherally, by RuO4 are island phases containing thermoplastic polyurethane elastomers (B), while unstained, grayish-white island phases are island phases containing polyethylene (D).

[0510] As a transmission electron microscope, the model used is the H-7650 transmission electron microscope manufactured by Hitachi Advanced Technology Co., Ltd., with the magnification set to 40,000x.

[0511] The diameter of the island phase was determined by image analysis using WinRoof 2018 image processing software manufactured by Mitani Corporation. Specifically, the area of ​​25.5 μm formed by a vertical dimension of 4.25 μm and a horizontal dimension of 6.00 μm was obtained from the image. 2 The rectangular region is set as the resolution range (field area). Island phases containing thermoplastic polyurethane elastomer (B) or polyethylene (D) are binarized separately. The number of each island phase is counted, and the equivalent circle diameter is calculated. The arithmetic mean of the equivalent circle diameters of the island phases calculated based on the number of island phases containing thermoplastic polyurethane elastomer (B) and their equivalent circle diameters is set as the average diameter of the island phases containing thermoplastic polyurethane elastomer (B). The arithmetic mean of the equivalent circle diameters of the island phases calculated based on the number of island phases containing polyethylene (D) and their equivalent circle diameters is set as the average diameter of the island phases containing polyethylene (D).

[0512] The area ratio of the island phase containing thermoplastic polyurethane elastomer (B) is set as the total area of ​​the island phase containing thermoplastic polyurethane elastomer (B) divided by 25.5 μm of the analytical range. 2 The value obtained.

[0513] [1.3] Peak intensity, crystallinity, and ratio (peak intensity / crystallinity) of α-crystals

[0514] Wide-angle X-ray diffraction apparatus (Empyrean, Spectris Co., Ltd.), X-ray source: CuKα, output power: 45kV, 40mA, detector: PIXcel. 3D Fibers cut from spunbond nonwoven fabric, excluding the embossed portion, are filled into a sample holder, and wide-angle X-ray diffraction profile measurements are performed while the holder is rotated. Based on the diffraction profile results obtained from the wide-angle X-ray diffraction profile measurements, the peak area originating from the crystalline region and the halo area originating from the amorphous region are calculated, and the crystallinity is calculated using the following formula.

[0515] Crystallinity [%] = Peak area originating from crystalline regions / (Peak area originating from crystalline regions + Halo area originating from amorphous regions) × 100

[0516] Based on the diffraction profile results, the maximum peak intensity (peak intensity of α crystal) of the (110) plane representing the propylene polymer (A) near 2θ=14° is determined.

[0517] Calculate the ratio of peak intensity to crystallinity of the α crystal (peak intensity / crystallinity).

[0518] [1.4] Average fiber diameter

[0519] Using an electron microscope (Hitachi S-3500N), photographs of the fibers of the spunbond nonwoven fabric were taken at 1000x magnification. Based on the obtained photographs, the diameter of the fibers whose diameter could be measured was determined. The photographs and measurements were repeated until the total number of fibers measured was greater than 100. The arithmetic mean of the obtained fiber diameters was taken as the average fiber diameter (μm).

[0520] [1.5] Pay per payment

[0521] Ten 250mm (machine direction: MD) × 200mm (transverse direction: CD) test pieces were collected from spunbond nonwoven fabric. The test pieces were collected at 10 arbitrary locations along both the MD and CD directions of the spunbond nonwoven fabric. Then, the mass (g) of each test piece was measured using an electronic balance (manufactured by Kensei Kogyo Co., Ltd.). The average mass of each test piece was calculated. The calculated average mass was then converted to per m³. 2 The mass (g) is rounded to the first decimal place, and the resulting value is set as g / m³. 2 〕.

[0522] [1.6] Tensile strength, strength index, and ratio (strength index / visible weight)

[0523] The tensile strength of spunbond nonwoven fabrics was tested according to JIS L 1906. Test pieces with a width of 25 mm and a length of 200 mm were collected from the spunbond nonwoven fabric. Using a tensile testing machine, with a clamping distance of 100 mm and a machine head speed of 100 mm / min, 5 MD and 5 CD samples were tested. The average value of each sample was calculated, and the tensile strength (N / 25 mm) of MD and CD was determined.

[0524] The strength index and ratio (strength index / mesh) are calculated using the following formulas (X1) and (X2).

[0525] Equation (X1): Strength index = (((tensile strength of MD)) 2 +(Tensile strength of CD) 2 ) / 2) 0.5

[0526] Formula (X2): Ratio (strength index / strip) = Strength index / strip

[0527] The permissible range for (strength index / strain) is 0.7 [(N / 25mm) / (g / m²)]. 2 )]above.

[0528] [1.7] Maximum elongation of MD (%) and maximum elongation of CD (%)

[0529] For spunbond nonwoven fabrics, according to JIS L 1906 6.12.1 [Method A], five test pieces with a machine direction (MD) of 25 cm and a cross direction (CD) of 5 cm were collected in a constant temperature chamber of 20±2℃ and 65±2% as specified in JIS Z 8703 (standard conditions of the test site). Tensile tests were conducted on the obtained test pieces using a tensile testing machine (Instron 5564 model, manufactured by Instron Japan) under the conditions of a clamping distance of 100 mm and a tensile speed of 300 mm / min. The elongation at which the tensile load of the five test pieces was measured, which is the average of their maximum values, was defined as the maximum elongation (%), and used as an index for evaluating elongation. Specifically, the maximum elongation (%) of MD was calculated using the following formula (X3), and the maximum elongation (%) of CD was calculated using the following formula (X4).

[0530] Formula (X3): Maximum elongation (%) = {(first maximum length - 25cm) / 25cm} × 100

[0531] Formula (X4): Maximum elongation (%) = {(Second maximum length - 5cm) / 5cm} × 100

[0532] In Equation (X3), the "first maximum length" refers to the length (cm) of the test piece when the tensile strength is shown in the MD direction. In Equation (X4), the "second maximum length" refers to the length (cm) of the test piece when the tensile strength is shown in the CD direction.

[0533] The permissible range for maximum elongation of MD is 190% or more. The permissible range for maximum elongation of CD is 150% or more.

[0534] [1.8] Breathability

[0535] For a total of 5 locations, including the center and four corners, of the spunbond nonwoven fabric (100mm×100mm), the air permeability was measured using a Fraser-type testing machine according to JIS L1096 at a pressure difference of 125Pa. The average value of the measured values ​​was set as the air permeability.

[0536] The permissible range for air permeability is 280 cm. 3 / cm 2 · seconds] or more.

[0537] [1.9] Evenness Index (Geometry Index)

[0538] For spunbond nonwovens, the uniformity index was set as the average value of the uniformity index with n=5 using Nomura Corporation's "FMT-MIII" formulation tester. The smaller the uniformity index, the better the uniformity.

[0539] The uniformity index is represented by 10σ / E. σ is the standard deviation of the density non-uniformity of the spunbond nonwoven fabric, and E can be obtained by measuring the light transmittance (T) of the spunbond nonwoven fabric. Represented by E = 2 - logT, when the transmittance is close to 100% (poor uniformity), E≈0, and the uniformity index shows an infinite value.

[0540] [1.10] Theoretical resin density

[0541] The theoretical resin density is calculated using the following formula (X5).

[0542] Formula (X5): Theoretical resin density (g / cm³) 3 )=1÷(Σ(composition ratio(-) / density(g / cm³)) 3 )))

[0543] Σ(composition ratio (-) / density (g / cm³) 3 = Proportion of propylene homopolymer (A-1) relative to the total amount of the resin composition (mass%) / Density of propylene homopolymer (A-1) (g / cm³) 3 The percentage of thermoplastic polyurethane elastomer (B-1) relative to the total amount of the resin composition (mass%) / density of thermoplastic polyurethane elastomer (B-1) (g / cm³) 3 The percentage of polymer (C-1) relative to the total amount of the resin composition (mass%) / density of polymer (C-1) (g / cm³) 3 The percentage of polymer (C-2) relative to the total amount of the resin composition (mass%) / density of polymer (C-2) (g / cm³) 3 )

[0544] It should be noted that the density of the propylene homopolymer (A-1) described later is set to 0.91 g / cm³. 3 The density of TPU(B-1), described later, is set to 1.20 g / cm³. 3 The density of the polymer (C-1) described later is set to 0.91 g / cm³. 3 The density of the polymer (C-2) described later is set to 0.95 g / cm³. 3 The density of polyethylene (D-1) described later is set to 0.95 g / cm³. 3 .

[0545] [1.11] Thickness

[0546] Ten 100mm (machine orientation: MD) × 100mm (transverse orientation: CD) test pieces were collected from spunbond nonwoven fabric. The thickness at the center was measured, and the average value of the ten pieces was calculated. This average value was taken as the thickness. A load of 125gf / cm was used for the thickness measurement.2 (probe diameter is) ) thickness gauge.

[0547] [1.12] Fiber filling rate and porosity

[0548] The fiber filling rate (equivalent to the amount of fiber per unit volume) of spunbond nonwoven fabric is expressed by the following formula (X6). The porosity (the amount of voids per unit volume) of spunbond nonwoven fabric is expressed by the following formula (X7).

[0549] Formula (X6): Fiber filling rate (%) = (Approximate weight (g / m³)) 2 Thickness (mm) / Theoretical resin density (g / cm³) 3 () / 1000)×100

[0550] Formula (X7): Porosity (%) = 100 - Fiber Filling Rate (%)

[0551] [2] Preparation

[0552] [2.1] Preparation of propylene polymer (A)

[0553] As a propylene-based polymer (A), an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.91 g / cm³ were prepared. 3 A propylene homopolymer (A-1) with a melting point (Tm) of 160℃.

[0554] [2.2] Manufacturing of thermoplastic polyurethane elastomer (B)

[0555] The following is a method for manufacturing TPU (B-1) as a thermoplastic polyurethane elastomer (B). 71.7 parts by weight of a polyester polyol with a number average molecular weight of 1932, 4.8 parts by weight of 1,4-butanediol (hereinafter also referred to as "BD"), 0.3 parts by weight of pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (hereinafter referred to as "antioxidant-1"), and 0.3 parts by weight of polycarbodiimide are mixed. 22.9 parts by weight of 4,4'-diphenylmethane diisocyanate (hereinafter also referred to as "MDI") are added. After thorough high-speed mixing, the mixture is reacted at 160°C for 1 hour.

[0556] After pulverizing the reactants, 0.8 parts by weight of ethylene bis-stearamide, 0.5 parts by weight of triethylene glycol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (hereinafter also referred to as "antioxidant-2"), and 0.8 parts by weight of ethylene bis-oleamide (hereinafter also referred to as "EOA") were mixed with 100 parts by weight of the pulverized reactants. The mixture was then melt-blended and granulated using an extruder (set temperature: 210°C) to obtain TPU (B-1).

[0557] The physical properties of the obtained TPU (B-1) are as follows: Shore A hardness: 82, melting point (Tm) (high melting point side): 162.2℃, heat of fusion: 11.4mJ / mg, solidification onset temperature: 155℃, heat of fusion ratio of hard zone: 0.58, and melt viscosity: 1100Pa·s.

[0558] [2.3] Preparation of polymer (C)

[0559] As the polymer (C-1), Tuftec "Grade MP10" (type: amine-modified hydrogenated styrene thermoplastic elastomer, polar group: amino, main chain: hydrogenated styrene block copolymer) manufactured by Asahi Kasei Corporation is used.

[0560] As the polymer (C-2), UMEX "Grade1001" (type: carboxylic anhydride modified polypropylene resin, polar group: carboxylic anhydride group, main chain: polyolefin) manufactured by Sanyo Chemical Industry Co., Ltd. is used.

[0561] [2.4] Preparation of Polymer (I)

[0562] As polymer (I), Tuftec "Grade H1053" (type: hydrogenated styrene thermoplastic elastomer, polar groups: not detected, main chain: hydrogenated styrene block copolymer) manufactured by Asahi Kasei Corporation was used.

[0563] [2.5] Preparation of Polyethylene (D)

[0564] As for polyethylene (D-1), the MFR (measured according to ASTM D1238 at 190°C and a load of 2.16 kg) was 5 g / 10 minutes, and the density was 0.95 g / cm³. 3 Polyethylene with a melting point (Tm) of 134℃.

[0565] [3] Examples and Comparative Examples

[0566] [3.1] Example 1

[0567] use Figure 1 The manufacturing apparatus shown is used to produce spunbond nonwoven fabric as follows. Using... The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 80.6% by mass of propylene homopolymer (A-1), 16.1% by mass of TPU (B-1), and 3.2% by mass of polymer (C-1) with a melting point (Tm) of 160℃ was melted. The melted mixture was then spun using a spunbond nonwoven fabric manufacturing apparatus with a spinneret having an orifice diameter of 0.6 mm and 1093 orifices. The mixture was spun under the following conditions: resin temperature and mold temperature both 205℃, cooling air temperature 20℃ (mixture single-orifice discharge rate: 0.60 g / min, stretching air velocity 4190 m / min), and piled onto a collecting belt. It was then subjected to heat and pressure treatment using an embossing roller (embossing area ratio (heat bonding rate) 18%, embossing temperature 120℃), producing a total fabric weight of 30 g / m². 2 spunbond nonwoven fabric. The term "stretch air velocity" refers to the flow rate of the cooling air (Nm³). 3 / minute) relative to the cross-sectional area of ​​the neck of the stretching part (m²) 2 The ratio of ).

[0568] [3.2] Comparative Example 1

[0569] The stretching air velocity in Example 1 was changed from 4190 m / min to 2841 m / min. Otherwise, the same operation as in Example 1 was performed to produce a total fabrication weight of 30 g / m. 2 spunbond nonwoven fabric.

[0570] [3.3] Comparative Example 2

[0571] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 83.3% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C and 16.7% by mass of TPU (B-1) were melted, and otherwise the same operation as in Example 1 was performed. However, many filament breaks occurred during the spinning stage, making it impossible to produce spunbond nonwoven fabric.

[0572] Therefore, the sample was prepared according to the following procedure for transmission electron microscopy observation and wide-angle X-ray diffraction measurement. The fiber content of the above mixture was adjusted to 30 g / m². 2 The spunbond nonwoven fabric is stacked on any fabric in a certain way and heated and pressed together with the fabric using an embossing roller (embossing area ratio (heat pressing rate) 18%, embossing temperature 120℃). The spunbond nonwoven fabric is peeled off from the embossed laminate and used as a sample for testing.

[0573] [3.4] Comparative Example 3

[0574] The stretching air velocity of Comparative Example 2 was changed from 4190 m / min to 2841 m / min. Otherwise, the same operation as in Comparative Example 2 was performed to produce a total aggregate weight of 30 g / m. 2 spunbond nonwoven fabric.

[0575] [3.5] Comparative Example 4

[0576] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 96.2% by mass of propylene homopolymer (A-1) and 3.8% by mass of polymer (C-1) with a melting point (Tm) of 160°C was melted, and otherwise the same operation as in Example 1 was performed to produce a total aggregate weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0577] [3.6] Comparative Example 5

[0578] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 100.0% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C was melted, and otherwise the same operation as in Example 1 was performed to produce a total aggregate weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0579] [3.7] Example 2

[0580] use The extruder achieved an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 75.8% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C, 16.1% by mass of TPU (B-1), 3.2% by mass of polymer (C-1), and 4.8% by mass of polyethylene (D-1) was melted, and then the same procedure as in Example 1 was performed to produce a total aggregate weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0581] [3.8] Example 3

[0582] The polymer (C-1) in Example 2 was replaced with polymer (C-2), and all other operations were performed in the same manner as in Example 2 to produce a total feed weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0583] [3.9] Comparative Example 6

[0584] The polymer (C-1) in Example 2 was replaced with polymer (I), and all other operations were performed in the same manner as in Example 2. Many broken filaments were generated during the spinning stage, making it impossible to produce a spunbond nonwoven fabric. Therefore, the preparation of samples for transmission electron microscopy observation and wide-angle X-ray diffraction measurement was carried out according to the method described in Comparative Example 2.

[0585] [3.10] Comparative Example 7

[0586] The stretching air velocity of Comparative Example 5 was changed from 4190 m / min to 2841 m / min. Otherwise, the same operation as in Comparative Example 6 was performed to produce a total attachment weight of 30 g / m. 2 spunbond nonwoven fabric.

[0587] [3.11] Comparative Example 8

[0588] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 78.3% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C, 16.7% by mass of TPU (B-1), and 5.0% by mass of polyethylene (D-1) was melted, and otherwise the same operation as in Example 1 was performed. Many filament breaks occurred during the spinning stage, making it impossible to manufacture spunbond nonwoven fabric. Therefore, the preparation of samples for transmission electron microscopy observation and wide-angle X-ray diffraction measurement was carried out according to the method described in Comparative Example 2.

[0589] [3.12] Comparative Example 9

[0590] The stretching air velocity of Comparative Example 6 was changed from 4190 m / min to 2841 m / min. Otherwise, the same operation as in Comparative Example 8 was performed to produce a total aggregate weight of 30 g / m. 2 spunbond nonwoven fabric.

[0591] [3.13] Comparative Example 10

[0592] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³.3 A mixture of 90.4% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C, 3.8% by mass of polymer (C-1), and 5.8% by mass of polyethylene (D-1) was melted, and otherwise the same operation as in Example 1 was performed to produce a total aggregate weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0593] [3.14] Comparative Example 11

[0594] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 94.0% by mass of propylene homopolymer (A-1) and 6.0% by mass of polyethylene (D-1) with a melting point (Tm) of 160°C was melted, and otherwise the same operation as in Example 1 was performed to produce a total aggregate weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0595] [3.15] Example 4

[0596] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 86.2% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C, 4.6% by mass of TPU (B-1), 3.7% by mass of polymer (C-1), and 5.5% by mass of polyethylene (D-1) was melted, and then the same procedure as in Example 1 was performed to produce a total aggregate weight of 29 g / m³. 2 spunbond nonwoven fabric.

[0597] [3.16] Comparative Example 12

[0598] use The extruder was used to achieve an MFR (measured according to ASTM D1238 at 230°C and a load of 2.16 kg) of 60 g / 10 min and a density of 0.910 g / cm³. 3 A mixture of 89.5% by mass of propylene homopolymer (A-1) with a melting point (Tm) of 160°C, 4.8% by mass of TPU (B-1) and 5.7% by mass of polyethylene (D-1) was melted, and otherwise the same operation as in Example 1 was performed to produce a total aggregate weight of 30 g / m³. 2 spunbond nonwoven fabric.

[0599] [Table 1]

[0600]

[0601] [Table 2]

[0602]

[0603] As shown in Tables 1 and 2, for the spunbond nonwoven fabrics of Examples 1 to 4, the resin composition comprises a propylene polymer (A), a thermoplastic polyurethane elastomer (B), and a polymer (C). The specific (peak strength / crystallinity) is 10.5 or less [strength [count] / %]. The stretching air velocity is 3000 m / min or more. Therefore, the specific (strength index / mesh) of Examples 1 to 4 is 0.70 [(N / 25mm) / (g / m²)]. 2 The above. The air permeability of Examples 1 to 4 is 280 cm⁻¹. 3 / cm 2 • More than 2 seconds. These results show that the spunbond nonwoven fabrics of Examples 1 to 4 have excellent tensile strength and high air permeability.

[0604] For the spunbond nonwoven fabric of Comparative Example 1, the resin composition comprises a propylene polymer (A), a thermoplastic polyurethane elastomer (B), and a polymer (C). The specific (peak strength / crystallinity) is greater than 10.5 [strength [count] / %]. The stretching air velocity is less than 3000 m / min. Therefore, the specific (strength index / finishing weight) of Comparative Example 1 is less than 0.70 [(N / 25mm) / (g / m³)]. 2 )〕.

[0605] For the spunbond nonwoven fabrics of Comparative Examples 2, 6, and 8, the resin composition contained a propylene-based polymer (A) and a thermoplastic polyurethane-based elastomer (B), but no polymer (C). The ratio (peak strength / crystallinity) was greater than 10.5 [strength [count] / %]. The stretching air velocity was 3000 m / min or higher. Therefore, in Comparative Examples 2, 6, and 8, many filament breaks occurred during the spinning stage, making it impossible to manufacture spunbond nonwoven fabrics.

[0606] For the spunbond nonwoven fabrics of Comparative Examples 3, 7, and 9, the resin composition contains a propylene polymer (A) and a thermoplastic polyurethane elastomer (B), but no polymer (C). The specific strength (peak intensity / crystallinity) is greater than 10.5 [strength [count] / %]. The stretching air velocity is less than 3000 m / min. Therefore, the specific strength index (strength index / finishing weight) of Comparative Examples 3, 7, and 9 is less than 0.70 [(N / 25mm) / (g / m³)]. 2 )〕.

[0607] For the spunbond nonwoven fabrics of Comparative Examples 4 and 10, the resin composition contains a propylene polymer (A) and a polymer (C), but does not contain a thermoplastic polyurethane elastomer (B). The specific strength (peak intensity / crystallinity) is greater than 10.5 [strength [count] / %]. The stretching air velocity is 3000 m / min or higher. Therefore, the specific strength index (strength index / mesh weight) of Comparative Examples 4 and 10 is less than 0.70 [(N / 25mm) / (g / m³)]. 2 The air permeability of Comparative Examples 4 and 10 is less than 280 cm³. 3 / cm 2 ·Second.

[0608] For the spunbond nonwoven fabric of Comparative Example 5, the resin composition contains a propylene polymer (A) but does not contain a thermoplastic polyurethane elastomer (B) or a polymer (C). The ratio (peak strength / crystallinity) is greater than 10.5 [strength [count] / %]. The stretching air velocity is 3000 m / min or higher. Therefore, the air permeability of Comparative Example 5 is less than 280 cm⁻¹. 3 / cm 2 ·Second.

[0609] For the spunbond nonwoven fabric of Comparative Example 11, the resin composition contains a propylene polymer (A) and polyethylene (D-1), but does not contain a thermoplastic polyurethane elastomer (B) and polymer (C). The specific (peak strength / crystallinity) is greater than 10.5 [strength [count] / %]. The stretching air velocity is 3000 m / min or more. Therefore, the specific (strength index / finishing weight) of Comparative Example 11 is less than 0.70 [(N / 25mm) / (g / m³)]. 2 Comparative Example 11 has an air permeability of less than 280 cm⁻¹. 3 / cm 2 ·Second.

[0610] For the spunbond nonwoven fabric of Comparative Example 12, the resin composition contains a propylene polymer (A), a thermoplastic polyurethane elastomer (B), and polyethylene (D-1), but does not contain polymer (C). The ratio (peak strength / crystallinity) is greater than 10.5 [strength [count] / %]. The stretching air velocity is 3000 m / min or higher. Therefore, the air permeability of Comparative Example 12 is less than 280 cm⁻¹. 3 / cm 2 ·Second.

[0611] These results show that the spunbond nonwoven fabrics of Comparative Examples 1 to 12 do not meet the requirements of excellent tensile strength and high air permeability.

[0612] The full disclosure of Japanese Patent Application 2022-057478, filed on March 30, 2022, is incorporated herein by reference.

[0613] All documents, patent applications and technical standards described in this specification are incorporated herein by reference to the same extent as those documents, patent applications and technical standards specifically described herein and incorporated herein by reference.

Claims

1. A spunbond nonwoven fabric comprising fibers formed from a resin composition, The resin composition comprises propylene polymer A, nucleating agent b, and polymer C. The polymer C is modified by at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups. The content of the propylene polymer A relative to the total amount of the resin composition is 70.0% to 97.0% by mass. The content of the nucleating agent b relative to the total amount of the resin composition is 2.0% to 20.0% by mass. The content of polymer C relative to the total amount of the resin composition is 1.0% to 10.0% by mass. The fiber has an island structure. The marine phase contained in the island structure includes the propylene polymer A. The island phase contained in the island structure includes the crystallizing nucleating agent b. The ratio of the peak intensity of the α crystal of the fiber to the crystallinity of the fiber is less than 10.5, and the unit of this ratio is intensity [count] / %. The peak intensity and crystallinity of the α crystal were obtained in the following manner: The X-ray diffraction apparatus used was an Empyrean manufactured by Spectris Corporation. The X-ray source was CuKα, with an output power of 45 kV and 40 mA. The detector was a PIXcel. 3D Fibers cut from spunbond nonwoven fabric, excluding the embossed portion, are filled into the sample holder. Wide-angle X-ray diffraction profile measurements are performed while the holder is rotated. Based on the diffraction profile results obtained from the wide-angle X-ray diffraction profile measurements, the peak area originating from the crystalline region and the halo area originating from the amorphous region are calculated. The crystallinity is then calculated using the following formula: Crystallinity [%] = Peak area originating from crystalline regions / (Peak area originating from crystalline regions + Halo area originating from amorphous regions) × 100 Based on the diffraction profile results, the maximum peak intensity of the (110) plane representing the propylene polymer (A) near 2θ=14° is determined, which is the peak intensity of the α crystal.

2. The spunbond nonwoven fabric according to claim 1, wherein the nucleating agent b is a thermoplastic polyurethane elastomer B.

3. The spunbond nonwoven fabric according to claim 2, when used with a transmission electron microscope at 25.5 μm... 2 When observing a cross-section orthogonal to the axial direction of the fiber using the field of view area, The island phase comprising the thermoplastic polyurethane elastomer B has an average diameter of 0.095 μm or less, and The number of island phases comprising the thermoplastic polyurethane elastomer B is 200 or more.

4. The spunbond nonwoven fabric according to any one of claims 1 to 3, wherein the polar group comprises at least one of an oxygen-containing group and a nitrogen-containing group.

5. The spunbond nonwoven fabric according to any one of claims 1 to 3, wherein the polar group comprises at least one selected from the group consisting of amino, carboxyl, carboxylic anhydride and ester groups.

6. The spunbond nonwoven fabric according to claim 5, wherein the polar group comprises an amino group.

7. The spunbond nonwoven fabric according to any one of claims 1 to 3, wherein the main chain of the polymer C comprises a polyolefin or a hydrogenated styrene block copolymer.

8. The spunbond nonwoven fabric according to any one of claims 1 to 3, wherein the propylene polymer A comprises a propylene homopolymer with a melting point of 140°C or higher.

9. The spunbond nonwoven fabric according to any one of claims 1 to 3, wherein the resin composition further comprises a density of 0.941 g / cm³. 3 ~0.970g / cm 3 Polyethylene D.

10. The spunbond nonwoven fabric according to claim 9, wherein the content of polyethylene D is 1.0% to 10.0% by mass relative to the total amount of the resin composition.

11. The spunbond nonwoven fabric according to claim 9, when viewed under a transmission electron microscope at 25.5 μm... 2 When observing a cross-section orthogonal to the axial direction of the fiber using the field of view area, The island phase containing the polyethylene D has an average diameter of less than 0.11 μm, and The number of island phases comprising the polyethylene D is 150 or more.

12. The spunbond nonwoven fabric according to any one of claims 1 to 3, wherein the ratio of the peak intensity of the α crystal of the fiber to the crystallinity of the fiber is 8.5 to 10.5, and the unit of the ratio is intensity [count] / .

13. A sanitary material comprising the spunbond nonwoven fabric according to any one of claims 1 to 12.

14. A method for manufacturing a spunbond nonwoven fabric, wherein, The resin composition is melt-spun to form a continuous fiber assembly, and the continuous fiber assembly is stretched using cooling air. The resin composition comprises a propylene polymer A, a thermoplastic polyurethane elastomer B, and a polymer C, wherein polymer C is modified with at least one polar group selected from the group consisting of oxygen-containing groups, nitrogen-containing groups, sulfur-containing groups, and phosphorus-containing groups. The content of the propylene polymer A relative to the total amount of the resin composition is 70.0% to 97.0% by mass. The content of the thermoplastic polyurethane elastomer B relative to the total amount of the resin composition is 2.0% to 20.0% by mass. The content of polymer C relative to the total amount of the resin composition is 1.0% to 10.0% by mass. The cooling air velocity is above 3000 m / min.

Citation Information

Patent Citations

  • Method for the recyclable production of plastic products, recyclable plastic product, method for operating a data processing system, and data processing system

    DE102019127827A1

  • Production of ethylenic wax

    JP1996239414A

  • Mixed fiber, and stretch nonwoven fabric comprising the mixed fiber and method for manufacture thereof

    JP2004244791A

  • Polishing pad

    JP2022057478A

  • Spun-bonded nonwoven fabric

    WO2007091444A1